Adhesive composition for dental use
By using a specific combination of dental adhesive compositions, the problems of insufficient filming and mechanical strength in the use of cured substances in the prior art are solved, and the long-term high mechanical strength and filming are achieved to improve the bonding strength and adaptability of the tooth quality.
Patent Information
- Application Number
- CN202380061432.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-25
- Filing Date
- 2023-08-24
- Publication Date
- 2025-04-04
AI Technical Summary
The existing dental adhesive compositions are difficult to take into account the filming of cured substances and the long-term and continuous high mechanical strength during resin coating applications, which affects the adaptability of dental patches and bridging teeth.
The dental adhesive composition is used that contains monomers with acid groups, multifunctional monomers without acid groups, polymerization initiators, water, volatile organic solvents and fillers. By adjusting the type of monomers, compounding ratio and viscosity, the water absorption rate and mechanical strength of the cured product are controlled.
The filmization of the cured substance and long-term continuous high mechanical strength are achieved, the bonding strength of the tooth and the cavities are improved, and the cavities are sealed. It is suitable for resin coating and indirect repair methods.
Smart Images

Figure BDA0005281394370000151 
Figure BDA0005281394370000351 
Figure BDA0005281394370000421
Abstract
Description
Technical Field
[0001] The present invention relates to a dental adhesive composition. More specifically, the present invention relates to a dental adhesive composition that achieves both thin film formation of a cured product and high mechanical strength that lasts for a long period of time. Background Art
[0002] Adhesive materials are used to repair and treat biological hard tissues such as wet bodies (for example, tooth structure, bone, etc.) As adhesive materials used for wet bodies, resin-based curable compositions containing radical polymerizable monomers, polymerization initiators, etc. are generally used.
[0003] Teeth that have lost their functions due to caries or accidents are repaired by fixing dental prostheses such as metal or ceramic crown restoration materials called inlays or crowns to the teeth. In order to fix the crown restoration material to the teeth, an adhesive called dental resin cement is used.
[0004] Regarding dental treatment, there are two methods, namely, a "direct restoration method" in which a dental restoration material made of a composite resin is directly filled into a cavity, and an "indirect restoration method" in which the aforementioned crown restoration material is fixed to the tooth.
[0005] In the indirect restoration method, during the period until the dental prosthesis is produced, the following operations are generally performed: sealing with a temporary sealing material to protect the tooth-forming surface or attaching a temporary restoration using a temporary adhesive material.
[0006] Under such circumstances, the following method (hereinafter referred to as the resin coating method) has been proposed: for the purpose of improving the adhesion of dental resin adhesives, improving the adaptability of the inner surface of restorations, and protecting exposed dentin, a dental adhesive is applied to the cavity formation surface just after a cavity is formed and before an impression is obtained to protect the exposed dentin and pulp, and then a temporary restoration such as a temporary sealing material and a temporary bonding material is installed, and thereafter, the adhesion between the dental resin adhesive and the dentin is intended to be improved.
[0007] Dental adhesives used in the resin coating method require a thin coating layer so as not to affect the shape of the abutment tooth to be formed, and high adhesion to the dentin and high mechanical strength of the coating layer are required to protect the exposed dentin. In particular, the adhesive is likely to accumulate on the edge of the abutment tooth in response to the shape of the abutment tooth to be formed, and the effect becomes greater when the viscosity of the adhesive is high. In fact, there are also reports that the shape of the abutment tooth coated by the resin coating method changes, which may affect the compatibility of the dental prosthesis with the abutment tooth (Non-Patent Document 1).
[0008] Regarding dental adhesives, in the direct restoration method that has been generally used so far, it is not required to reduce the thickness of the adhesive layer, and reducing the thickness is a required characteristic unique to the resin coating method.
[0009] Furthermore, the mechanical strength of a coating layer generally depends on the thickness of the coating layer, and therefore, the mechanical strength of a coating layer that is thinned generally decreases.
[0010] As dental adhesives, a one-step adhesive system is generally used in recent years, wherein the one-step adhesive system uses a one-component dental adhesive (one-component adhesive material) having the functions of a self-etching pretreatment agent and an adhesive material. The one-component adhesive material generally contains an acidic monomer, a hydrophilic monomer, a crosslinking monomer, etc. as monomer components, and a (meth)acrylate compound is generally used as a monomer component.
[0011] In order to improve the mechanical strength of the cured product, Patent Document 1 proposes the following adhesive material, which includes: a non-conjugated carbon chain with more than 4 carbons continuously bonded, 2 or more polymerizable groups and a polymerizable monomer with more than 2 hydroxyl groups; a polymerizable monomer with more than 1 polymerizable group and more than 1 aromatic ring; 2-hydroxyethyl methacrylate, 10-methacryloyloxy decamethylenephosphoric acid, water, ethanol, a polymerization accelerator, and a filler. Patent Document 2 proposes the following dental adhesive, which includes: a polymerizable monomer component containing a polymerizable monomer containing an acidic group, water, and a photopolymerization initiator composed of a diaryliodonium salt compound and a thioxanthone compound. Patent Document 3 proposes the following dental adhesive composition, which includes: a polymerizable monomer containing an acidic group, a water-soluble (meth)acrylate polymerizable monomer, water, a curing agent, and a cross-linking polymerizable monomer having at least 3 polymerizable groups and a hydrocarbon group formed by continuous bonding of at least 6 carbon atoms in a straight chain or a ring in the molecule.
[0012] Prior art literature
[0013] Patent Literature
[0014] Patent Document 1: Japanese Patent Application Publication No. 2008-260751
[0015] Patent Document 2: Japanese Patent Application Publication No. 2007-223955
[0016] Patent Document 3: Japanese Patent Application Publication No. 2005-179282
[0017] Non-patent literature
[0018] Non-patent literature 1: 2021 Autumn Academic Conference of the Japanese Society of Conservative Dentistry (155th) O1 Summary of the invention
[0019] Problems to be solved by the invention
[0020] It is also considered to apply the dental adhesive materials of Patent Documents 1 to 3 to resin coating applications. However, the present inventors have found that Patent Documents 1 and 3 have room for improvement in satisfying the required properties for resin coating applications due to the high water absorption of the cured products.
[0021] Furthermore, the composition of Patent Document 2 has insufficient mechanical strength when used for resin coating.
[0022] As described above, in the prior art, there is still room for improvement in dental adhesive compositions suitable for resin coating applications that have the following properties: the ability to make the cured product into a sufficiently thin film to a degree that does not affect the compatibility of dental restorations and bridge abutments, and the ability to have excellent mechanical strength for a long period of time to protect the exposed dentin.
[0023] Therefore, an object of the present invention is to provide a dental adhesive composition capable of achieving both thin film formation of a cured product and high mechanical strength that lasts for a long period of time.
[0024] Means used to solve problems
[0025] The present inventors have conducted intensive studies and found that a dental adhesive composition containing specific components and having specific parameters can solve the above-mentioned problems. The inventors have further conducted studies and have completed the present invention.
[0026] That is, the present invention includes the following technical solutions.
[0027] [1] A dental adhesive composition comprising: a monomer having an acidic group (A), a monomer having no acidic group (B), a polymerization initiator (C), water (D), a volatile organic solvent (E), and a filler (F);
[0028] The monomer (B) having no acidic group includes: a monomer (B-1) having three or more polymerizable groups in one molecule, a hydrophobic monomer (B-2) having one or two polymerizable groups in one molecule, and a hydrophilic monomer (B-3) having one or two polymerizable groups in one molecule.
[0029] The viscosity based on B-type viscometer at 30°C is less than 40cps,
[0030] The water absorption of the cured product was 4.0% or less.
[0031] [2] The dental adhesive composition according to [1], wherein the monomer (B-1) having three or more polymerizable groups in one molecule contains a hydrophobic compound.
[0032] [3] The dental adhesive composition according to [1] or [2], wherein the monomer (B-1) having three or more polymerizable groups in one molecule contains a compound having a urethane bond.
[0033] [4] The dental adhesive composition according to any one of [1] to [3], wherein the monomer (B-1) having three or more polymerizable groups in one molecule contains an aliphatic compound.
[0034] [5] The dental adhesive composition according to any one of [1] to [4], wherein the content of the monomer (B-1) having three or more polymerizable groups in one molecule is 0.1 to 20 parts by mass in 100 parts by mass of all monomer components.
[0035] [6] The dental adhesive composition according to any one of [1] to [5], wherein the polymerizable group possessed by the monomer (B-1) having three or more polymerizable groups in one molecule is a (meth)acryloyloxy group.
[0036] [7] The dental adhesive composition according to any one of [1] to [6], wherein the polymerization initiator (C) comprises at least one selected from the group consisting of (bis)acylphosphine oxides, α-diketones, and coumarins.
[0037] [8] The dental adhesive composition according to any one of [1] to [7], wherein the volatile organic solvent (E) contains an alcohol solvent.
[0038] [9] The dental adhesive composition according to any one of [1] to [8], wherein at least one of the monomer (B-1) having three or more polymerizable groups in one molecule, the hydrophobic monomer (B-2) having one or two polymerizable groups in one molecule, and the hydrophilic monomer (B-3) having one or two polymerizable groups in one molecule contains a monomer having a (meth)acrylamide group.
[0039]
[10] The dental adhesive composition according to [9], wherein the hydrophobic monomer (B-2) having one or two polymerizable groups in one molecule includes a monomer having a (meth)acrylamide group.
[0040]
[11] The dental adhesive composition according to any one of [1] to
[10] , wherein the monomer (A) having an acidic group includes a monomer having a phosphate group and having one polymerizable group in one molecule.
[0041]
[12] The dental adhesive composition according to
[11] , wherein the content of the monomer having a phosphate group and having one polymerizable group per molecule is 90 parts by mass or more in a total of 100 parts by mass of the monomer (A) having an acidic group contained in the dental adhesive composition.
[0042]
[13] The dental adhesive composition according to any one of [1] to
[12] , wherein the monomer (B-1) having three or more polymerizable groups in one molecule comprises a hydrophobic compound, and all the polymerizable groups possessed by the hydrophobic compound are (meth)acryloyloxy groups.
[0043]
[14] The dental adhesive material according to any one of [1] to
[13] .
[0044]
[15] The dental coating material according to any one of [1] to
[13] .
[0045] Effects of the Invention
[0046] According to the present invention, a dental adhesive composition that can achieve both thin film formation of a cured product and high mechanical strength that can be sustained over a long period of time can be provided. The dental adhesive composition of the present invention has excellent durability, and therefore, even when used in the oral cavity for a long period of time, it can achieve both thin film formation of a cured product and high mechanical strength that can be sustained over a long period of time.
[0047] The dental adhesive composition of the present invention also has excellent bonding strength to tooth structure over a long period of time, and can continuously protect exposed tooth structure over a long period of time in resin coating applications, and can be suitably used in indirect restoration methods.
[0048] The dental adhesive composition of the present invention has high mechanical strength for a long time even if the thickness of the coating is 12 μm or less (preferably 10 μm or less, more preferably less than 7 μm) in resin coating applications requiring thin filming. Therefore, even if the layer of the cured product formed after an operation to volatilize the solvent component (air blowing, etc.) becomes thinner than expected due to changes in the thickness of the layer depending on the location due to the degree of air blowing, the mechanical strength of the cured product will not continue to decrease for a long time. Therefore, from the viewpoint of not requiring strict operation during use, it is particularly advantageous in resin coating applications.
[0049] Furthermore, the dental adhesive composition of the present invention is also excellent in adhesive strength to tooth structure and exhibits good caries sealing properties, and therefore can be suitably used as a dental adhesive composition for a general direct restoration method. DETAILED DESCRIPTION
[0050] The dental adhesive composition of the present invention comprises: a monomer having an acidic group (A), a monomer having no acidic group (B), a polymerization initiator (C), water (D), a volatile organic solvent (E) and a filler (F).
[0051] The monomer (B) having no acidic group includes: a monomer (B-1) having three or more polymerizable groups in one molecule, a hydrophobic monomer (B-2) having one or two polymerizable groups in one molecule, and a hydrophilic monomer (B-3) having one or two polymerizable groups in one molecule.
[0052] The viscosity based on B-type viscometer at 30°C is less than 40cps,
[0053] The water absorption of the cured product was 4.0% or less.
[0054] In the present specification, "(meth)acrylic" is a general term for methacrylic and acrylic, and the same applies to expressions similar thereto ("(meth)acrylic acid", "(meth)acrylonitrile", etc.).
[0055] In this specification, a "monofunctional monomer" refers to a monomer having one polymerizable group in one molecule.
[0056] In this specification, the upper limit and lower limit of the numerical range (content of each component, value calculated from each component, each physical property, etc.) can be combined appropriately. In addition, in this specification, each embodiment can be combined appropriately with each other.
[0057] In general, in the composition, a polyfunctional monomer such as a monomer (B-1) having three or more polymerizable groups in one molecule has an effect of improving mechanical strength, but there is a problem that the polymerization shrinkage becomes larger due to the increased curing property. Furthermore, since the content of the polyfunctional monomer in the entire composition increases, the content of the monofunctional monomer that has permeability to the tooth substance decreases relatively, thereby causing a problem that the permeability of the composition to the tooth substance decreases and the bonding strength to the tooth substance decreases.
[0058] Furthermore, the present inventors have found that when the content of a multifunctional monomer such as a monomer (B-1) having three or more polymerizable groups in one molecule of the entire composition is increased, without compounding a hydrophobic monomer having one or two polymerizable groups in one molecule, the hydrophobicity cannot be sufficiently improved to the level required for resin coating applications. As a result, the water absorption of the cured product cannot be sufficiently reduced, and in resin coating applications, both a thin film and high mechanical strength of the coating layer cannot be achieved.
[0059] Furthermore, in the resin coating method, it is difficult to achieve both high mechanical strength and thin film formation of the coating layer. Therefore, it is even more difficult to realize a dental adhesive composition in which the cured product formed into a thin film has high mechanical strength for a long period of time.
[0060] As described above, it is clear that simply increasing the content of a multifunctional monomer such as a monomer (B-1) having three or more polymerizable groups in one molecule cannot achieve both long-term protection of the dentin exposed by caries formation and thinning of the cured product of the dental adhesive composition, i.e., the coating layer, for the purpose of not affecting the shape of the formed abutment tooth.
[0061] On the other hand, the reason why the dental adhesive composition of the present invention can achieve both thin film formation of the cured product and high mechanical strength sustained over a long period of time is not clear, but can be presumed as follows.
[0062] In the present invention, a monomer (A) having an acidic group, a monomer (B) not having an acidic group (including a monomer (B-1) having three or more polymerizable groups in one molecule, a hydrophobic monomer (B-2) having one or two polymerizable groups in one molecule, and a hydrophilic monomer (B-3) having one or two polymerizable groups in one molecule), a polymerization initiator (C), water (D), a volatile organic solvent (E) and a filler (F) are constituted in appropriate types and blending ratios so that they function as a whole, and the dental adhesive composition can be made low in viscosity. Thus, the filmization of the cured product can be achieved. It can be further inferred that by making the composition have both high curability and moderate hydrophobicity, the occurrence of components or their action mechanisms that reduce the mechanical strength of the cured product can be suppressed, and high mechanical strength that lasts for a long time can be obtained.
[0063] The viscosity of the dental adhesive composition of the present invention at 30°C is less than 40 cps. By having a viscosity within this range, the cured product can be made thinner, and the influence on the compatibility of the dental prosthesis and the bridge abutment can be suppressed. In addition, by being included within this range, the formed adhesive layer can be made very thin, and further, combined with the condition that the water absorption rate of the cured product is a predetermined ratio, it works integrally, not only can the adhesive layer be made very thinner, but also the reduction in mechanical strength can be suppressed, and high mechanical strength can be continuously exhibited for a long time.
[0064] The viscosity can be adjusted by appropriately combining the type, blending ratio and viscosity of the monomers, the type and content of the filler, the content of water, the type and content of the volatile organic solvent, and the like.
[0065] The viscosity is adjusted as follows.
[0066] Generally speaking, the more the number of polymerizable groups in a monomer, the higher the viscosity. In addition, if the monomer contains a part that interacts within and between molecules, the viscosity of the monomer becomes higher. For example, if the monomer contains a functional group with hydrogen bonding such as a hydroxyl group or an NH2 group, the viscosity of the monomer becomes higher, and even if it has ionic bonding, its viscosity becomes higher. In the case where the monomer contains an aromatic ring, the viscosity of the monomer also becomes higher. Considering the mechanical strength of the cured product, the adhesion to the tooth substance, etc., the type, mixing ratio and viscosity of the monomer can be appropriately changed.
[0067] In the present invention, the viscosity can be adjusted to a desired range by using a monomer (B-1) having three or more polymerizable groups in one molecule and a monomer having one or two polymerizable groups in one molecule (a hydrophobic monomer (B-2) having one or two polymerizable groups in one molecule, a hydrophilic monomer (B-3) having one or two polymerizable groups in one molecule) in combination, and further combining with a filler (F) and a solvent (water (D), a volatile organic solvent (E)).
[0068] There is a tendency that the smaller the particle size of the filler is, the greater the thickening effect of the dental adhesive composition is.
[0069] The thickening effect is affected by the presence or absence of surface treatment. For example, when a filler without surface treatment is used, the thickening effect becomes greater because the hydroxyl groups present on the filler surface interact with other components in the dental adhesive composition.
[0070] The type and content of the filler may be appropriately adjusted in consideration of the mechanical strength of the cured product, the adhesiveness to tooth structure, and the like.
[0071] There is a tendency that the viscosity of the dental adhesive composition decreases as the content of water and volatile organic solvent increases. When the dental adhesive composition is applied to tooth substance, water and volatile organic solvents will hinder curing and reduce the mechanical strength of the cured product, so it is necessary to volatilize them by blowing air. Therefore, it is necessary to adjust the water and volatile organic solvent to an appropriate content. Considering the mechanical strength of the cured product, the adhesiveness to tooth substance and other characteristics, the water content, the type and content of the volatile organic solvent can be appropriately adjusted.
[0072] From the viewpoint of thin film formation and mechanical strength of the cured product, the viscosity at 30° C. using a B-type viscometer is less than 40 cps, preferably 5 to 40 cps, more preferably 10 to 40 cps, further preferably 15 to 35 cps, and particularly preferably 20 to 30 cps. The viscosity is measured as described in the Examples.
[0073] The water absorption of the cured product of the dental adhesive composition of the present invention is 4.0% or less. By having a water absorption within this range, the coating layer can be made thinner and have excellent mechanical strength in the resin coating application. By containing the above range, the cured product has excellent adhesion and mechanical strength to tooth texture, and combined with the condition of the specified viscosity, it works as a whole, and does not simply stop at excellent mechanical strength, but further has these characteristics (adhesion to tooth texture, mechanical strength) for a long time. Such a cured product also has excellent durability.
[0074] The water absorption of the cured product can be adjusted according to the type and blending ratio of the monomers, the type and amount of the polymerization initiator, the type, amount and ratio of the polymerization accelerator to the polymerization accelerator, the type, particle size and content of the filler, the amount of water, and the type and amount of the volatile organic solvent. Among the above, the desired water absorption can be easily obtained by adjusting the type and blending ratio of the monomers. By adjusting other components such as the polymerization initiator within the range described in this specification, it is easier to adjust to the desired water absorption.
[0075] The water absorption rate is adjusted as follows.
[0076] Regarding monomers, generally speaking, the more hydrophilic functional groups such as hydroxyl groups, ether bonds, and amines a monomer has, the higher its water absorption rate becomes, and the water absorption rate of monomers without such functional groups becomes lower.
[0077] The larger the particle size of the filler, the smaller the specific surface area becomes, the less water adheres to the surface, and thus the water absorption rate becomes lower. On the other hand, if the particle size is small, the more water adheres to the surface, and thus the water absorption rate becomes higher.
[0078] Filler is hydrophobized on the surface by surface treatment, and water absorption rate decreases. The more hydrophobized on the surface is carried out, the more water absorption rate can be reduced. In order to improve the hydrophobicity of filler, following method can also be considered: use filler (for example, inorganic filler with silicon dioxide as main component etc.) with many hydroxyl number on the surface, carry out dehydration condensation reaction by surface treatment. In addition, by using the high filler type of hydrophobicity in advance, water absorption rate can also be reduced.
[0079] As for the increase in water absorption, the hydrophilic monomer has a greater influence on the filler and the hydrophilic monomer. Therefore, the more the filler content is and the less the hydrophilic monomer content is, the lower the water absorption becomes, and the less the filler content is and the more the hydrophilic monomer content is, the higher the water absorption tends to be. In addition, generally speaking, the water absorption of organic fillers tends to be higher than that of inorganic fillers and organic-inorganic composite fillers.
[0080] From the viewpoint of mechanical strength of the cured product, adhesion to tooth texture, and durability thereof, the water absorption of the cured product of the dental adhesive composition of the present invention is 4.0% or less, preferably 3.5% or less, more preferably 3.0% or less, further preferably 2.5% or less, and particularly preferably less than 2.3%. If the water absorption exceeds 4.0%, the long-term mechanical strength and adhesion to tooth texture of the cured product may be insufficient.
[0081] The method for measuring the water absorption is as described in the examples.
[0082] In addition, in the resin coating method, from the viewpoint of being able to achieve thin film formation and easily obtaining high mechanical strength that lasts for a long time, the dental adhesive composition of the present invention is preferably such that the water absorption of the cured product after its cured product is immersed in distilled water at 37°C for 7 days is 7.5% or less, more preferably 7.0% or less, further preferably 6.5% or less, and particularly preferably less than 6.0%.
[0083] The method for measuring the water absorption of the cured product after immersion in distilled water at 37° C. for 7 days is as described in the Examples.
[0084] Hereinafter, each component used for the dental adhesive composition of the present invention will be described.
[0085] <Monomer having an acidic group (A)>
[0086] In the dental adhesive composition, the monomer (A) having an acidic group is essential from the viewpoint of adhesion to tooth. By compounding the monomer (A) having an acidic group, excellent adhesion to tooth can be achieved. A free radical polymerizable monomer is preferably used in the dental adhesive composition.
[0087] Specific examples of radical polymerizable monomers in the monomer (A) having an acidic group include (meth)acrylate monomers, (meth)acrylamide monomers, α-cyanoacrylic acid, α-haloacrylic acid, esters of crotonic acid, cinnamic acid, sorbic acid, maleic acid, itaconic acid, etc., vinyl esters, vinyl ethers, mono-N-vinyl derivatives, styrene derivatives, etc. Among these, (meth)acrylate monomers and (meth)acrylamide monomers whose polymerizable groups are (meth)acryloyloxy groups and (meth)acrylamide groups are preferred from the viewpoint of curability.
[0088] The monomer (A) having an acidic group is preferably a monomer having one or two polymerizable groups in one molecule (a monofunctional monomer or a bifunctional polymer), and more preferably a monomer having one polymerizable group in one molecule, from the viewpoint of excellent adhesion to tooth substance (especially dentin) and the ability to easily suppress the increase in viscosity of the dental adhesive composition when combined with other monomers.
[0089] Examples of the monomer (A) having an acidic group used in the present invention include monomers having at least one acidic group such as a phosphoric acid group, a pyrophosphate group, a thiophosphoric acid group, a phosphonic acid group, a carboxylic acid group, or a sulfonic acid group.
[0090] The monomer (A) having an acidic group may be used alone or in appropriate combination of two or more. Specific examples of the monomer (A) having an acidic group are as follows.
[0091] Examples of the monomer having a phosphate group include 2-(meth)acryloyloxyethyl dihydrogen phosphate, 3-(meth)acryloyloxypropyl dihydrogen phosphate, 4-(meth)acryloyloxybutyl dihydrogen phosphate, 5-(meth)acryloyloxypentyl dihydrogen phosphate, 6-(meth)acryloyloxyhexyl dihydrogen phosphate, 7-(meth)acryloyloxyheptyl dihydrogen phosphate, 8-(meth)acryloyloxyoctyl dihydrogen phosphate, 9-(meth)acryloyloxynonyl dihydrogen phosphate, 10-(meth)acryloyloxydecyl dihydrogen phosphate, 11-(meth)acryloyloxyundecyl dihydrogen phosphate, 12-(meth)acryloyloxydodecyl dihydrogen phosphate, 16-(meth)acryloyloxyhexadecyl dihydrogen phosphate, 20-(meth)acryloyloxyeicosyl dihydrogen phosphate, 2-(meth)acryloyloxyethylphenyl hydrogen phosphate, 2-(meth)acryloyloxyethylphenyl hydrogen phosphate, and 2-(meth)acryloyloxyethylphenyl hydrogen phosphate. Monofunctional monomers such as acryloyloxyethyl (2-bromoethyl), 2-methacryloyloxyethyl (4-methoxyphenyl) hydrogen phosphate, and 2-methacryloyloxypropyl (4-methoxyphenyl) hydrogen phosphate; difunctional monomers such as bis (2-(meth)acryloyloxyethyl) hydrogen phosphate, bis (4-(meth)acryloyloxybutyl) hydrogen phosphate, bis (6-(meth)acryloyloxyhexyl) hydrogen phosphate, bis (8-(meth)acryloyloxyoctyl) hydrogen phosphate, bis (9-(meth)acryloyloxynonyl) hydrogen phosphate, bis (10-(meth)acryloyloxydecyl) hydrogen phosphate, 1,3-glycerol di(meth)acrylate phosphate (also known as 1,3-di(meth)acryloyloxypropyl dihydrogen phosphate), and acid chlorides, alkali metal salts, and amine salts thereof, preferably monomers having an alkylene group having 6 to 12 carbon atoms and a divalent phosphoric acid group.
[0092] As a preferred embodiment, there is mentioned a dental adhesive composition in which the monomer (A) having an acidic group includes a monomer having a phosphoric acid group and having one polymerizable group in one molecule.
[0093] As another suitable embodiment, there can be mentioned the following dental adhesive composition, wherein the content of the monomer having a phosphate group and having one polymerizable group in one molecule is 90 parts by mass or more in a total of 100 parts by mass of the monomer (A) having an acidic group contained in the dental adhesive composition.
[0094] In the above embodiment, the content of the monomer having a phosphate group and having one polymerizable group in one molecule is preferably 92 parts by mass or more, more preferably 95 parts by mass or more, further preferably 98 parts by mass or more, and particularly preferably 100 parts by mass in a total of 100 parts by mass of the monomer having an acidic group (A).
[0095] As another preferred embodiment, there is mentioned a dental adhesive composition in which the monomer (A) having an acidic group contains a monomer having an alkylene group having 6 to 12 carbon atoms and a divalent phosphoric acid group.
[0096] In any of the above-mentioned preferred embodiments, the polymerizable group contained in the monomer is preferably a (meth)acryloyloxy group.
[0097] Examples of the monomer having a pyrophosphate group include bis[2-(meth)acryloyloxyethyl] pyrophosphate, bis[4-(meth)acryloyloxybutyl] pyrophosphate, bis[6-(meth)acryloyloxyhexyl] pyrophosphate, bis[8-(meth)acryloyloxyoctyl] pyrophosphate, bis[10-(meth)acryloyloxydecyl] pyrophosphate, and acid chlorides, alkali metal salts, and amine salts thereof.
[0098] Examples of the monomer having a thiophosphoric acid group include 2-(meth)acryloyloxyethyl dihydrogen thiophosphate, 3-(meth)acryloyloxypropyl dihydrogen thiophosphate, 4-(meth)acryloyloxybutyl dihydrogen thiophosphate, 5-(meth)acryloyloxypentyl dihydrogen thiophosphate, 6-(meth)acryloyloxyhexyl dihydrogen thiophosphate, 7-(meth)acryloyloxyheptyl dihydrogen thiophosphate, 8-(meth)acryloyloxyoctyl dihydrogen thiophosphate, 9-(meth)acryloyloxynonyl dihydrogen thiophosphate, 10-(meth)acryloyloxydecyl dihydrogen thiophosphate, 11-(meth)acryloyloxyundecyl dihydrogen thiophosphate, 12-(meth)acryloyloxydodecyl dihydrogen thiophosphate, 16-(meth)acryloyloxyhexadecyl dihydrogen thiophosphate, 20-(meth)acryloyloxyeicosyl dihydrogen thiophosphate, and acid chlorides, alkali metal salts, and ammonium salts thereof.
[0099] Examples of the monomer having a phosphonic acid group include 2-(meth)acryloyloxyethylphenyl phosphonate, 5-(meth)acryloyloxypentyl-3-phosphopropionate, 6-(meth)acryloyloxyhexyl-3-phosphopropionate, 10-(meth)acryloyloxydecyl-3-phosphopropionate, 6-(meth)acryloyloxyhexyl-3-phosphoacetate, 10-(meth)acryloyloxydecyl-3-phosphoacetate, and acid chlorides, alkali metal salts, and ammonium salts thereof.
[0100] Examples of the monomer having a carboxylic acid group include monofunctional (meth)acrylates having one carboxyl group or an acid anhydride group thereof in one molecule and monofunctional (meth)acrylates having a plurality of carboxyl groups or an acid anhydride groups thereof in one molecule.
[0101] Examples of the monofunctional monomer having one carboxyl group or anhydride group thereof in one molecule include (meth)acrylic acid, N-(meth)acryloylglycine, N-(meth)acryloylaspartic acid, 2-(meth)acryloyloxyethyl hydrogen succinate, 2-(meth)acryloyloxyethyl hydrogen phthalate, 2-(meth)acryloyloxyethyl hydrogen maleate, O-(meth)acryloyltyrosine, N-(meth)acryloyltyrosine, N-(meth)acryloyloxyethyl The invention also includes 2-(meth)acryloylphenylalanine, N-(meth)acryloyl-p-aminobenzoic acid, N-(meth)acryloyl-o-aminobenzoic acid, 2-(meth)acryloyloxybenzoic acid, 3-(meth)acryloyloxybenzoic acid, 4-(meth)acryloyloxybenzoic acid, N-(meth)acryloyl-5-aminosalicylic acid, N-(meth)acryloyl-4-aminosalicylic acid, and compounds obtained by anhydriding the carboxyl groups of these compounds.
[0102] Examples of the monofunctional monomer having a plurality of carboxyl groups or acid anhydride groups thereof in one molecule include 6-(meth)acryloyloxyhexane-1,1-dicarboxylic acid, 9-(meth)acryloyloxynonane-1,1-dicarboxylic acid, 10-(meth)acryloyloxydecane-1,1-dicarboxylic acid, 11-(meth)acryloyloxyundecane-1,1-dicarboxylic acid, 12-(meth)acryloyloxydodecane-1,1-dicarboxylic acid, 13-(meth)acryloyloxytridecane-1,1-dicarboxylic acid, 4-(meth)acryloyloxyethyl trimellitate, 4-(meth)acryloyloxyacetic anhydride trimellitate, 4-(meth)acryloyloxybutyl trimellitate, 4-(meth)acryloyloxyhexyl trimellitate, 4-(meth)acryloyloxydecyl trimellitate, 2-(meth)acryloyloxyethyl-3'-(meth)acryloyloxy-2'-(3,4-dicarboxybenzoyloxy)propyl succinate, 6-(meth)acryloyloxyethylnaphthalene-1,2,6-tricarboxylic anhydride, 6-(meth)acryloyloxyethylnaphthalene-2,3,6-tricarboxylic anhydride, 4-(meth)acryloyloxyethylcarbonylpropionyl-1,8-naphthalene dicarboxylic anhydride, 4-(meth)acryloyloxyethylnaphthalene-1,8-tricarboxylic anhydride, and the like.
[0103] Examples of the monomer having a sulfonic acid group include 2-sulfoethyl (meth)acrylate and the like.
[0104] In addition, among the monomers (A) having an acidic group, from the viewpoint of good bonding strength of the dental adhesive composition to tooth substance, it is preferred to include a monomer having a phosphate group or a monomer having a carboxylic acid group, and more preferably 2-(meth)acryloxyethyl dihydrogen phosphate, 3-(meth)acryloxypropyl dihydrogen phosphate, 4-(meth)acryloxybutyl dihydrogen phosphate, 5-(meth)acryloxypentyl dihydrogen phosphate, 6-(meth)acryloxyhexyl dihydrogen phosphate, 7-(meth)acryloxyheptyl dihydrogen phosphate, 8-(meth)acryloxyoctyl dihydrogen phosphate, 9-(meth)acryloxynonyl dihydrogen phosphate, 10-(meth)acryloxydecyl dihydrogen phosphate, 11-(meth)acryloxyundecyl dihydrogen phosphate, 12-(meth)acryloxydodecyl dihydrogen phosphate, 16-(meth)acryloxyhexadecyl dihydrogen phosphate, 20-(meth)acryloxyeicosyl dihydrogen phosphate. Preferably, the present invention comprises an ester, 4-(meth)acryloyloxyethyl trimellitic anhydride, 4-(meth)acryloyloxyethyl trimellitic acid, 11-(meth)acryloyloxyundecane-1,1-dicarboxylic acid, and a mixture of 2-methacryloyloxyethyl dihydrogen phosphate and bis(2-methacryloyloxyethyl) hydrogen phosphate. More preferably, 8-(meth)acryloyloxyoctyl dihydrogen phosphate, 9-(meth)acryloyloxynonyl dihydrogen phosphate, 10-(meth)acryloyloxydecyl dihydrogen phosphate, 11-(meth)acryloyloxyundecyl dihydrogen phosphate, 12-(meth)acryloyloxydodecyl dihydrogen phosphate, 16-(meth)acryloyloxyhexadecyl dihydrogen phosphate, and 20-(meth)acryloyloxyeicosyl dihydrogen phosphate are used. In view of the ease of suppressing the increase in viscosity of the dental adhesive composition and the balance between the adhesive strength and the curability to the tooth substance, 10-(meth)acryloyloxydecyl dihydrogen phosphate is particularly preferred.
[0105] From the viewpoint of easily suppressing the increase in viscosity of the dental adhesive composition when combined with other monomers and from the viewpoint of adhesiveness to tooth texture, the content of the monomer (A) having an acidic group in the dental adhesive composition is preferably 1 to 50% by mass, more preferably 1 to 30% by mass, and even more preferably 3 to 20% by mass, based on the total mass of the dental adhesive composition.
[0106] <Monomer (B) Not Having an Acidic Group>
[0107] Examples of the monomer (B) having no acidic group in the present invention include a monomer (B-1) having three or more polymerizable groups in one molecule, a hydrophobic monomer (B-2) having one or two polymerizable groups in one molecule, and a hydrophilic monomer (B-3) having one or two polymerizable groups in one molecule.
[0108] Monomer having three or more polymerizable groups in one molecule (B-1)
[0109] The monomer (B-1) having three or more polymerizable groups in one molecule (hereinafter sometimes referred to as "polyfunctional monomer (B-1)") is used in the dental adhesive composition of the present invention to achieve both thin film thickness and high mechanical strength of the cured product.
[0110] Examples of the polymerizable group include a vinyl group, a (meth)acryloyloxy group, and a (meth)acrylamide group. From the viewpoint of easy free radical polymerization, a (meth)acryloyloxy group and / or a (meth)acrylamide group are preferred. From the viewpoint of adhesion to dentin, a (meth)acrylamide group is preferred.
[0111] The polyfunctional monomer (B-1) may be used alone or in combination of two or more.
[0112] The number of polymerizable groups possessed by the polyfunctional monomer (B-1) is 3 or more, and may be 4 or more. The upper limit of the number of polymerizable groups is not particularly limited, and may be 10 or less, and may be 6 or less.
[0113] The polyfunctional monomer (B-1) preferably contains a hydrophobic compound from the viewpoint of being able to sufficiently improve the hydrophobicity and further reduce the water absorption of the cured product.
[0114] As the hydrophobic compound, a compound having a solubility of less than 10% by mass in water at 25° C. is preferred. The hydrophobicity of the hydrophobic compound can be adjusted using a hydrophilic group. Examples of the hydrophilic group include at least one selected from a hydroxyl group, an oxymethylene group, an oxyethylene group, an oxypropylene group, and an amide group.
[0115] The hydrophobic compound is preferably a compound having no hydrophilic group, and more preferably a compound having no hydroxyl group.
[0116] As a preferred embodiment, there is mentioned a dental adhesive composition in which the hydrophobic compound includes a compound having 1 or less hydroxyl groups.
[0117] As another preferred embodiment, there is mentioned a dental adhesive composition in which all polymerizable groups possessed by the hydrophobic compound are (meth)acryloyloxy groups.
[0118] From the viewpoint of mechanical strength, the polyfunctional monomer (B-1) preferably contains a compound having a carbamate bond. In addition, from the viewpoint of viscosity, the polyfunctional monomer (B-1) preferably contains an aliphatic compound, and from the viewpoint of mechanical strength, it is more preferred to contain an aliphatic compound having a carbamate bond.
[0119] Examples of the polyfunctional monomer (B-1) include trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, trimethylolmethane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, ethoxylated pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol poly(meth)acrylate, ethoxylated dipentaerythritol poly(meth)acrylate, di(trimethylolpropane) tetramethacrylate, ethoxylated glycerol triacrylate, tris(2-(meth)acryloyloxyethyl)isocyanurate, N,N-(2,2,4-trimethylhexamethylene) Bis[2-(aminocarboxy)propane-1,3-diol]tetra(meth)acrylate, 1,7-diacryloxy-2,2,6,6-tetra(meth)acryloyloxymethyl-4-oxaheptane, N,N',N"-triacryloyldiethylenetriamine, N,N',N",N"'-tetraacryloyltriethylenetetramine, and compounds represented by the following formulas (1) to (3). Among these, trimethylolpropane tri(meth)acrylate, N,N-(2,2,4-trimethylhexamethylene)bis[2-(aminocarboxy)propane-1,3-diol]tetramethacrylate, bis(trimethylolpropane)tetramethacrylate, and N,N',N",N"'-tetraacryloyltriethylenetetramine are preferred from the viewpoint of mechanical strength.
[0120]
[0121] From the viewpoint of long-term sustained mechanical strength, viscosity and adhesion to tooth texture, the content of the monomer (B-1) having three or more polymerizable groups in one molecule in the dental adhesive composition of the present invention is preferably 0.1 to 20 mass %, more preferably 0.5 to 15 mass %, further preferably 1 to 10 mass %, and particularly preferably 2 to 8 mass % in the total mass of the dental adhesive composition.
[0122] By making the content of the monomer (B-1) having three or more polymerizable groups in one molecule less than 20 mass %, when it is combined with other components such as a hydrophobic monomer (B-2) having one or two polymerizable groups in one molecule, the hydrophobicity can be sufficiently improved, and the desired water absorption rate of the cured product can be easily obtained. When combined with a specified viscosity, in the resin coating method, it is possible to achieve both thin film formation of the coating layer and long-term excellent mechanical strength.
[0123] In addition, in a certain embodiment, the content of the monomer (B-1) having three or more polymerizable groups in one molecule is preferably 0.1 to 20 parts by mass, more preferably 0.5 to 15 parts by mass, further preferably 1 to 10 parts by mass, and particularly preferably 2 to 8 parts by mass in 100 parts by mass of all monomer components of the dental adhesive composition.
[0124] By making the content of the monomer (B-1) having three or more polymerizable groups in one molecule less than 20 parts by mass in 100 parts by mass of all monomer components of the dental adhesive composition, when it is combined with other components such as a hydrophobic monomer (B-2) having one or two polymerizable groups in one molecule, the hydrophobicity can be sufficiently improved, and the desired water absorption rate of the cured product can be easily obtained. When combined with a specified viscosity, in the resin coating method, both the thin film of the coating layer and the long-term excellent mechanical strength can be achieved.
[0125] ·Hydrophobic monomer (B-2)
[0126] The hydrophobic monomer (B-2) having one or two polymerizable groups in one molecule (hereinafter sometimes simply referred to as "hydrophobic monomer (B-2)") is a monomer having no acidic group and having a solubility in water at 25°C of less than 10% by mass.
[0127] The solubility of the hydrophobic monomer (B-2) in water at 25° C. is preferably less than 5% by mass, and more preferably less than 1% by mass.
[0128] The hydrophobic monomer (B-2) can improve the mechanical strength and durability (adhesive strength to tooth substance, mechanical strength) of the cured product of the dental adhesive composition and can reduce the water absorption rate.
[0129] As the hydrophobic monomer (B-2), a radical polymerizable monomer having no acidic group and having a polymerizable group is preferred.
[0130] Examples of the polymerizable group possessed by the hydrophobic monomer (B-2) include a vinyl group, a (meth)acryloyloxy group, and a (meth)acrylamide group. From the viewpoint of easy free radical polymerization, a (meth)acryloyloxy group and / or a (meth)acrylamide group are preferred, and from the viewpoint of adhesion to dentin, a (meth)acrylamide group is preferred.
[0131] As the hydrophobic monomer (B-2), from the viewpoint of water absorption, long-term mechanical strength, and adhesiveness to dentin, a compound having a (meth)acrylamide group and a (meth)acryloyloxy group is more preferably included, and a compound having an acrylamide group and a methacryloxy group is further preferably included.
[0132] The hydrophobic monomer (B-2) may be used alone or in combination of two or more.
[0133] Examples of the hydrophobic monomer (B-2) include a monofunctional monomer having one polymerizable group in one molecule and a bifunctional monomer having two polymerizable groups in one molecule.
[0134] Examples of the bifunctional monomer having two polymerizable groups in one molecule include aromatic compound-based bifunctional hydrophobic monomers and aliphatic compound-based bifunctional hydrophobic monomers.
[0135] Among the hydrophobic monomers (B-2), examples of the monofunctional monomers include monofunctional (meth)acrylate monomers of aliphatic compounds such as stearyl methacrylate; monofunctional (meth)acrylate monomers of aliphatic compounds having an ether bond such as butoxydiethylene glycol methacrylate and methoxypolyethylene glycol methacrylate (average number of moles of oxyethylene added: 9); monofunctional (meth)acrylate monomers of alicyclic compounds such as cyclohexyl methacrylate, isobornyl methacrylate and dicyclopentanyl methacrylate; monofunctional (meth)acrylate monomers having an aromatic ring group such as 2-phenoxyethyl methacrylate and phenoxybenzyl methacrylate; and monofunctional (meth)acrylate monomers having a heterocyclic group (e.g., a cyclic ether group) such as tetrahydrofurfuryl methacrylate.
[0136] As the monofunctional (meth)acrylate monomer having an aromatic ring group, one having one or two phenyl groups is preferred.
[0137] As the monofunctional (meth)acrylate monomer having a heterocyclic group, one having one or two heterocyclic groups (for example, a cyclic ether group, etc.) is preferred.
[0138] Among the monofunctional monomers, tetrahydrofurfuryl methacrylate (generally known as THF-MA), benzyl methacrylate (generally known as BEMA), phenoxybenzyl methacrylate (generally known as POB-MA), and 2-phenoxyethyl methacrylate (generally known as PEMA) are preferred from the viewpoint of mechanical strength and viscosity.
[0139] Examples of the aromatic compound-based bifunctional hydrophobic monomer include 2,2-bis((meth)acryloyloxyphenyl)propane, 2,2-bis[4-(3-(meth)acryloyloxy-2-hydroxypropoxy)phenyl]propane, 2,2-bis(4-(meth)acryloyloxyethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxypolyethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxydiethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxytriethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxytetraethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxy acryloyloxypentaethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxydipropoxyphenyl)propane, 2-(4-(meth)acryloyloxydiethoxyphenyl)-2-(4-(meth)acryloyloxyethoxyphenyl)propane, 2-(4-(meth)acryloyloxydiethoxyphenyl)-2-(4-(meth)acryloyloxytriethoxyphenyl)propane, 2-(4-(meth)acryloyloxydipropoxyphenyl)-2-(4-(meth)acryloyloxytriethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxypropoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxyisopropoxyphenyl)propane, and the like.
[0140] Among these, from the viewpoint of adhesion to tooth texture and mechanical strength, 2,2-bis[4-(2-hydroxy-3-methacryloxypropoxy)phenyl]propane (commonly referred to as "Bis-GMA"), 2,2-bis(4-(meth)acryloxyethoxyphenyl)propane, 2,2-bis(4-methacryloxypolyethoxyphenyl)propane (average number of added moles of ethoxy groups: 2.6, commonly referred to as "D-2.6E"), 2,2-bis(4-(meth)acryloxydiethoxyphenyl)propane, 2,2-bis(4-(meth)acryloxytriethoxyphenyl)propane, 2,2-bis(4-(meth)acryloxytetraethoxyphenyl)propane, and 2,2-bis(4-(meth)acryloxypentaethoxyphenyl)propane are preferred.
[0141] Examples of the aliphatic compound-based bifunctional hydrophobic monomer include glycerol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, butanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,5-pentanediol di(meth)acrylate, and 1,6-hexanediol di(meth)acrylate. Ester, 1,10-decanediol di(meth)acrylate, 2,2,4-trimethylhexamethylenebis(2-carbamoyloxyethyl) di(meth)acrylate, N-methacryloyloxyethyl acrylamide (commonly known as "MAEA"), N-methacryloyloxypropyl acrylamide, N-methacryloyloxybutyl acrylamide, N-(1-ethyl-(2-methacryloyloxy)ethyl)acrylamide, N-(2-(2-methacryloyloxyethoxy)ethyl)acrylamide, etc.
[0142] Among these, from the viewpoint of mechanical strength and handleability, triethylene glycol diacrylate, triethylene glycol dimethacrylate (commonly referred to as "3G"), neopentyl glycol dimethacrylate (commonly referred to as "NPG"), 2,2,4-trimethylhexamethylenebis(2-carbamoyloxyethyl) dimethacrylate (commonly referred to as "UDMA"), and 1,10-decanediol dimethacrylate (commonly referred to as "DD") are preferred.
[0143] From the viewpoint of polymerization shrinkage stress, UDMA and DD are preferred.
[0144] From the viewpoint of the adhesiveness to tooth structure, particularly dentin, N-methacryloxypropyl acrylamide (MAEA) is preferred.
[0145] Among the hydrophobic monomers (B-2), aromatic compound-based bifunctional hydrophobic monomers and aliphatic compound-based bifunctional hydrophobic monomers are preferably used from the viewpoints of water absorption, mechanical strength, solubility in water, and handling properties.
[0146] As the aromatic compound-based bifunctional monomer, Bis-GMA and D-2.6E are preferred.
[0147] As the aliphatic compound-based bifunctional monomer, 3G, neopentyl glycol di(meth)acrylate, UDMA, DD, and MAEA are preferred.
[0148] The amount of the hydrophobic monomer (B-2) in the dental adhesive composition is preferably 5 to 60% by mass, more preferably 10 to 50% by mass, further preferably 12 to 45% by mass, particularly preferably 15 to 40% by mass, based on the total mass of the dental adhesive composition.
[0149] When the content of the hydrophobic monomer (B-2) is below the upper limit value described below, wettability of the dental adhesive composition to tooth substance and decrease in adhesive force can be easily suppressed, and when the content is above the lower limit value described above, desired mechanical strength and water absorption of the cured product can be easily obtained.
[0150] ·Hydrophilic monomer (B-3)
[0151] The hydrophilic monomer (B-3) having one or two polymerizable groups in one molecule (hereinafter sometimes simply referred to as "hydrophilic monomer (B-3)") is a monomer having no acidic group and having a solubility in water at 25°C of 10% by mass or more.
[0152] The hydrophilic monomer (B-3) preferably has a solubility in water at 25°C of 30% by mass or more, and more preferably is soluble in water at 25°C in any proportion.
[0153] The hydrophilic monomer (B-3) can improve the wettability of the dental adhesive composition to tooth and the permeability to tooth (enamel / dentin), thereby improving the bonding strength to tooth.
[0154] As the hydrophilic monomer (B-3), a radical polymerizable monomer having no acidic group and having a polymerizable group is preferred.
[0155] Examples of the polymerizable group possessed by the hydrophilic monomer (B-3) include a vinyl group, a (meth)acryloyloxy group, and a (meth)acrylamide group. From the viewpoint of easy free radical polymerization, a (meth)acryloyloxy group and / or a (meth)acrylamide group are preferred, and from the viewpoint of adhesion to dentin, a (meth)acrylamide group is preferred.
[0156] The hydrophilic monomer (B-3) may be blended alone or in combination of two or more.
[0157] As the hydrophilic monomer (B-3), one having a hydrophilic group such as a hydroxyl group, an oxymethylene group, an oxyethylene group, an oxypropylene group, or an amide group is preferred.
[0158] Examples of the hydrophilic monomer (B-3) include a monofunctional monomer having one polymerizable group in one molecule and a bifunctional monomer having two polymerizable groups in one molecule.
[0159] Among the hydrophilic monomers (B-3), examples of the monofunctional monomer include hydrophilic monofunctional (meth)acrylate monomers such as 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 1,3-dihydroxypropyl (meth)acrylate, 2,3-dihydroxypropyl (meth)acrylate, and 2-((meth)acryloyloxy)ethyltrimethylammonium chloride; and hydrophilic monofunctional (meth)acrylamide monomers such as N-hydroxymethyl (meth)acrylamide, N-hydroxyethyl (meth)acrylamide, N,N-bis(2-hydroxyethyl) (meth)acrylamide, N-methoxymethyl (meth)acrylamide, N-ethoxymethyl (meth)acrylamide, diacetone (meth)acrylamide, 4-(meth)acryloylmorpholine, N-trihydroxymethyl-N-methyl (meth)acrylamide, N,N-dimethylacrylamide, and N,N-diethylacrylamide.
[0160] Examples of the bifunctional monomer include hydrophilic bifunctional (meth)acrylate monomers such as polyethylene glycol di(meth)acrylate (average number of added ethylene oxide moles: 9 or more), 1,2-bis(3-(meth)acryloyloxy-2-hydroxypropyloxy)ethane, and 3-(meth)acryloyloxy-2-hydroxypropyl (meth)acrylate.
[0161] Among these hydrophilic monomers (B-3), from the viewpoint of adhesiveness to tooth texture, 2-hydroxyethyl (meth)acrylate, 2,3-dihydroxypropyl (meth)acrylate, and hydrophilic monofunctional (meth)acrylamide-based monomers are preferred, and 2-hydroxyethyl (meth)acrylate, N,N-dimethylacrylamide, and N,N-diethylacrylamide are more preferred.
[0162] From the viewpoint of adhesion to tooth texture, the content of the hydrophilic monomer (B-3) in the dental adhesive composition is preferably 5 to 60% by mass, more preferably 7 to 50% by mass, further preferably 10 to 45% by mass, and particularly preferably 13 to 40% by mass, based on the total mass of the dental adhesive composition.
[0163] When the content of the hydrophilic monomer (B-3) in the dental adhesive composition is at least the above lower limit, a sufficient effect of improving the adhesive strength can be easily obtained, and when it is at most the above upper limit, desired mechanical strength and water absorption of the cured product can be easily obtained.
[0164] From the viewpoint of achieving both thin film formation and long-term mechanical strength of the cured product, the content of the monomer (B) having no acidic group in the dental adhesive composition is preferably 20 to 95% by mass, more preferably 25 to 90% by mass, and even more preferably 30 to 85% by mass, based on the total mass of the dental adhesive composition.
[0165] In addition, from the viewpoint of adhesion to tooth texture and water absorption of the cured product, the mass ratio of the hydrophobic monomer (B-2) to the hydrophilic monomer (B-3) is preferably hydrophobic monomer (B-2):hydrophilic monomer (B-3) = 1:0.1 to 1:3, more preferably 1:0.2 to 1:2, further preferably 1:0.3 to 1:1, and particularly preferably 1:0.4 to 1:0.9.
[0166] In addition, in a suitable embodiment, when combined with other structures such as a specified viscosity and a filler, the content of the hydrophobic monomer (B-2) is preferably greater than that of the multifunctional monomer (B-1) from the viewpoint that the dental adhesive composition can obtain moderate hydrophobicity, the water absorption rate of the cured product can be easily adjusted, and the higher mechanical strength of the cured product can be easily obtained for a long time. From the above viewpoint, the mass ratio of the multifunctional monomer (B-1) to the hydrophobic monomer (B-2) is preferably multifunctional monomer (B-1): hydrophobic monomer (B-2) = 1:1.1 to 1:500, more preferably 1:1.2 to 1:300, and further preferably 1:1.3 to 1:200.
[0167] In another suitable embodiment, when combined with other components such as a predetermined viscosity and a filler, the content of the hydrophilic monomer (B-3) is preferably greater than that of the multifunctional monomer (B-1) from the viewpoint of being able to obtain a higher bonding strength to the tooth substance and a higher mechanical strength of the cured product over a long period of time. From the above viewpoint, the mass ratio of the multifunctional monomer (B-1) to the hydrophilic monomer (B-3) is preferably multifunctional monomer (B-1): hydrophilic monomer (B-3) = 1:1.1 to 1:150, more preferably 1:1.2 to 1:100, and even more preferably 1:1.3 to 1:80.
[0168] In another suitable embodiment, the dental adhesive composition can be listed below, wherein at least one of the monomer (B-1) having three or more polymerizable groups in one molecule, the hydrophobic monomer (B-2) having one or two polymerizable groups in one molecule, and the hydrophilic monomer (B-3) having one or two polymerizable groups in one molecule contains a monomer having a (meth)acrylamide group.
[0169] In the above preferred embodiment, the hydrophobic monomer (B-2) and / or the hydrophilic monomer (B-3) preferably includes a monomer having a (meth)acrylamide group, and the hydrophobic monomer (B-2) more preferably includes a monomer having a (meth)acrylamide group.
[0170] For example, when the hydrophobic monomer (B-2) includes a monomer having a (meth)acrylamide group, the hydrophobic monomer (B-2) may include a monomer having an acrylamide group.
[0171] <Polymerization Initiator (C)>
[0172] In order to cure the monomer, a polymerization initiator (C) is an essential component. The polymerization initiator (C) can improve the mechanical strength and durability (adhesion strength and mechanical strength to tooth substance) of the cured product of the dental adhesive composition, and can reduce the water absorption rate. As the polymerization initiator (C), a photopolymerization initiator (C-1) or a chemical polymerization initiator (C-2) can be used, and one of each can be mixed alone, or two or more can be used in combination.
[0173] Photopolymerization initiator (C-1)
[0174] From the viewpoint of adhesion to tooth substance, curability, and mechanical strength, the dental adhesive composition preferably contains a photopolymerization initiator (C-1).
[0175] As the photopolymerization initiator (C-1), it is preferred to use a non-water-soluble photopolymerization initiator having a solubility of less than 10 g / L in water at 25°C (hereinafter sometimes referred to as "non-water-soluble photopolymerization initiator") or a water-soluble photopolymerization initiator having a solubility of 10 g / L or more in water at 25°C (hereinafter sometimes referred to as "water-soluble photopolymerization initiator"). From the viewpoint of curability and mechanical strength, it is preferred to contain a non-water-soluble photopolymerization initiator. In addition, in a certain embodiment, from the viewpoint of adhesion to tooth texture, a water-soluble photopolymerization initiator may be used in addition to the non-water-soluble photopolymerization initiator.
[0176] As the photopolymerization initiator (C-1), a known photopolymerization initiator may be used, and one type may be blended alone or two or more types may be blended in combination.
[0177] Examples of the water-insoluble photopolymerization initiator include (bis)acylphosphine oxides, thioxanthones, ketals, α-diketones, coumarins, anthraquinones, benzoin alkyl ether compounds, and α-aminoketone compounds.
[0178] Among the aforementioned (bis)acylphosphine oxides, examples of the acylphosphine oxides include 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 2,6-dimethoxybenzoyldiphenylphosphine oxide, 2,6-dichlorobenzoyldiphenylphosphine oxide, 2,4,6-trimethylbenzoylmethoxyphenylphosphine oxide, 2,4,6-trimethylbenzoylethoxyphenylphosphine oxide, 2,3,5,6-tetramethylbenzoyldiphenylphosphine oxide, and benzoylbis(2,6-dimethylphenyl)phosphonate. Examples of the bisacylphosphine oxides include bis(2,6-dichlorobenzoyl)phenylphosphine oxide, bis(2,6-dichlorobenzoyl)-2,5-dimethylphenylphosphine oxide, bis(2,6-dichlorobenzoyl)-4-propylphenylphosphine oxide, bis(2,6-dichlorobenzoyl)-1-naphthylphosphine oxide, bis(2,6-dimethoxybenzoyl)phenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,5-dimethylphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, and bis(2,5,6-trimethylbenzoyl)-2,4,4-trimethylpentylphosphine oxide.
[0179] Examples of the thioxanthones include thioxanthone and 2-chlorothioxan-9-one.
[0180] Examples of the ketals include benzyl dimethyl ketal and benzyl diethyl ketal.
[0181] Examples of the α-diketones include diacetyl, benzil, dl-camphorquinone, 2,3-pentanedione, 2,3-octanedione, 9,10-phenanthrenequinone, 4,4′-oxybiphenyl, and acenaphthenequinone. Among them, dl-camphorquinone is particularly preferred because it has a maximum absorption wavelength in the visible light region.
[0182] Examples of the coumarins include 3,3'-carbonylbis(7-diethylaminocoumarin), 3-(4-methoxybenzoyl)coumarin, 3-thenoylcoumarin, 3-benzoyl-5,7-dimethoxycoumarin, 3-benzoyl-7-methoxycoumarin, 3-benzoyl-6-methoxycoumarin, 3-benzoyl-8-methoxycoumarin, 3-benzoylcoumarin, 7-methoxy-3-(p-nitrobenzoyl)coumarin, 3-(p-nitrobenzoyl)coumarin, 3,5-carbonylbis(7-methoxycoumarin), 3-benzoyl-6-bromocoumarin, 3,3'-carbonylbiscoumarin, 3-benzoyl-7-dimethylaminocoumarin, 3-benzoyl-7-methoxycoumarin, benzo[f]coumarin, 3-carboxycoumarin, 3-carboxy-7-methoxycoumarin, 3-ethoxycarbonyl-6-methoxycoumarin, 3-ethoxycarbonyl-8-methoxycoumarin, 3-acetylbenzo[f]coumarin, 3-benzoyl-6-nitrocoumarin, 3-benzoyl-7-diethylaminocoumarin, 7-dimethylamino-3-(4-methoxybenzoyl)coumarin, 7-diethylamino-3-(4-methoxybenzoyl)coumarin, 7-diethylamino-3-(4-diethylamino)coumarin, 7-methoxy-3-(4-methoxybenzoyl)coumarin, 3-(4-nitrobenzoyl)benzo[f]coumarin, 3-(4-ethoxycinnamoyl)-7 -methoxycoumarin, 3-(4-dimethylaminocinnamoyl)coumarin, 3-(4-diphenylaminocinnamoyl)coumarin, 3-[(3-dimethylbenzothiazol-2-ylidene)acetyl]coumarin, 3-[(1-methylnaphtho[1,2-d]thiazol-2-ylidene)acetyl]coumarin, 3,3'-carbonylbis(6-methoxycoumarin), 3,3'-carbonylbis(7-acetoxycoumarin), 3,3'-carbonylbis(7-dimethylaminocoumarin), 3-(2-benzothiazolyl)-7-(diethylamino)coumarin, 3-(2-benzothiazolyl)-7-(dibutylamino)coumarin, 3-(2-benzimidazolyl)-7-(diethylamino)coumarin, 3-(2 -benzothiazolyl)-7-(dioctylamino)coumarin, 3-acetyl-7-(dimethylamino)coumarin, 3,3'-carbonylbis(7-dibutylaminocoumarin), 3,3'-carbonyl-7-diethylaminocoumarin-7'-bis(butoxyethyl)aminocoumarin, 10-[3-[4-(dimethylamino)phenyl]-1-oxo-2-propenyl]-2,3,6,7-tetrahydro-1,1,7,7-tetramethyl-1H,5H,11H-[1]benzopyrano[6,7,8-ij]quinolizin-11-one, 10-(2-benzothiazolyl)-2,3,6,7-tetrahydro-1,1,7,7-tetramethyl-1H,5H,11H-[1]benzopyrano[6,7,8-ij]quinolizin-11-one,8-ij]quinolizin-11-one and the like are compounds described in Japanese Patent Application Laid-Open No. 9-3109 and Japanese Patent Application Laid-Open No. 10-245525.
[0183] Among the above coumarins, 3,3'-carbonylbis(7-diethylaminocoumarin) and 3,3'-carbonylbis(7-dibutylaminocoumarin) are particularly suitable.
[0184] Examples of the anthraquinones include anthraquinone, 1-chloroanthraquinone, 2-chloroanthraquinone, 1-bromoanthraquinone, 1,2-benzanthraquinone, 1-methylanthraquinone, 2-ethylanthraquinone, and 1-hydroxyanthraquinone.
[0185] Examples of the benzoin alkyl ether compound include benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin isobutyl ether.
[0186] Examples of the α-aminoketone compound include 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropane-1-one and the like.
[0187] Among these water-insoluble photopolymerization initiators, at least one selected from (bis)acylphosphine oxides, α-diketones and coumarins is preferably included. Thus, a dental adhesive composition having excellent photocurability in the visible and near-ultraviolet regions and showing sufficient photocurability even when using any light source selected from halogen lamps, light-emitting diodes (LEDs) and xenon lamps can be obtained.
[0188] The water-soluble photopolymerization initiator can improve the polymerization curability at the hydrophilic tooth surface interface and achieve high bonding strength. The solubility of the water-soluble photopolymerization initiator in water at 25°C is 10 g / L or more, preferably 15 g / L or more, more preferably 20 g / L or more, and further preferably 25 g / L or more. By making the solubility 10 g / L or more, the water-soluble photopolymerization initiator is easily dissolved in the water in the tooth substance at the bonding interface, and the polymerization promotion effect is easily exhibited.
[0189] Examples of the water-soluble photopolymerization initiator include water-soluble thioxanthones; water-soluble acylphosphine oxides; a substance obtained by introducing a (poly)ethylene glycol chain into the hydroxyl group of 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propane-1-one, a substance obtained by introducing a (poly)ethylene glycol chain into the hydroxyl group and / or phenyl group of 1-hydroxycyclohexyl phenyl ketone, a substance obtained by introducing -OCH2COO2 into the phenyl group of 1-hydroxycyclohexyl phenyl ketone, - Na +A substance obtained by introducing a (poly)ethylene glycol chain into the hydroxyl group and / or phenyl group of 2-hydroxy-2-methyl-1-phenylpropane-1-one, a substance obtained by introducing -OCH2COO - Na + α-hydroxyalkyl acetophenones such as those obtained by quaternizing the amino group of α-aminoalkyl phenones such as 2-methyl-1[4-(methylthio)phenyl]-2-morpholinopropane-1-one and 2-benzyl-2-(dimethylamino)-1-[(4-morpholino)phenyl]-1-butanone, etc.
[0190] As the water-soluble thioxanthones, for example, 2-hydroxy-3-(9-oxo-9H-thioxanthen-4-yloxy)-N,N,N-trimethyl-1-propane ammonium chloride, 2-hydroxy-3-(1-methyl-9-oxo-9H-thioxanthen-4-yloxy)-N,N,N-trimethyl-1-propane ammonium chloride, 2-hydroxy-3-(9-oxo-9H-thioxanthen-2-yloxy)-N,N,N-trimethyl-1-propane ammonium chloride can be used. , 2-hydroxy-3-(3,4-dimethyl-9-oxo-9H-thioxanthen-2-yloxy)-N,N,N-trimethyl-1-propane ammonium chloride, 2-hydroxy-3-(3,4-dimethyl-9H-thioxanthen-2-yloxy)-N,N,N-trimethyl-1-propane ammonium chloride, 2-hydroxy-3-(1,3,4-trimethyl-9-oxo-9H-thioxanthen-2-yloxy)-N,N,N-trimethyl-1-propane ammonium chloride, etc.
[0191] Among these water-soluble acylphosphine oxides, sodium phenyl(2,4,6-trimethylbenzoyl)phosphinate, lithium phenyl(2,4,6-trimethylbenzoyl)phosphinate, sodium bis(2,4,6-trimethylbenzoyl)phosphinate and lithium bis(2,4,6-trimethylbenzoyl)phosphinate are preferred.
[0192] The content of the photopolymerization initiator (C-1) is not particularly limited, but is preferably 0.01 to 10% by mass, more preferably 0.05 to 7% by mass, and even more preferably 0.1 to 5% by mass, based on the total mass of the dental adhesive composition, from the viewpoint of the curability of the resulting dental adhesive composition.
[0193] Chemical polymerization initiator (C-2)
[0194] The dental adhesive composition may further contain a chemical polymerization initiator (C-2) from the viewpoint of enabling chemical polymerization and improving the cavity sealing property in a portion that light cannot reach.
[0195] The chemical polymerization initiator (C-2) may be used alone or in combination of two or more.
[0196] As the chemical polymerization initiator (C-2), an organic peroxide is preferred.
[0197] The organic peroxide used as the chemical polymerization initiator (C-2) is not particularly limited, and a known organic peroxide can be used.
[0198] Typical organic peroxides include ketone peroxide, hydrogen peroxide, diacyl peroxide, dialkyl peroxide, peroxyketal, peroxyester, peroxydicarbonate, etc. Specific examples of these organic peroxides include those described in International Publication No. 2008 / 087977.
[0199] The content of the chemical polymerization initiator (C-2) is not particularly limited, but is preferably 0.01 to 10% by mass, more preferably 0.05 to 7% by mass, and even more preferably 0.1 to 5% by mass, based on the total mass of the dental adhesive composition, from the viewpoint of the curability of the resulting dental adhesive composition.
[0200] <Water(D)>
[0201] The water (D) in the present invention promotes the decalcification of the monomer (A) having an acidic group. Water (D) needs to be water that does not substantially contain impurities that adversely affect adhesion, preferably distilled water or ion-exchanged water. In any case where the content of water (D) is too much or too little, the bonding strength to the tooth substance is sometimes reduced. The content of water (D) is preferably 1 to 50% by mass, more preferably 5 to 30% by mass, and further preferably 10 to 20% by mass in the total mass of the dental adhesive composition.
[0202] <Volatile organic solvent (E)>
[0203] In the dental adhesive composition of the present invention, from the viewpoint of bonding strength, coating property, thin film formation of the solidified product and preventing phase separation of each component for tooth substance, it is necessary to mix a volatile organic solvent (E). Since the volatile organic solvent (E) will become a factor in adjusting the viscosity of the dental adhesive composition, it can be integrated with other components to achieve thin film formation of the solidified product. In addition, as an organic solvent mixed in the dental adhesive composition of the present invention, from the viewpoint of application to the resin coating method and the like, it is necessary to be volatile.
[0204] The volatile organic solvent (E) may be used alone or in combination of two or more.
[0205] The volatile organic solvent (E) is preferably a water-soluble volatile organic solvent from the viewpoint of compatibility with the components in the dental adhesive composition. The volatile organic solvent preferably has a boiling point of 150° C. or less at normal pressure, and more preferably has a boiling point of 100° C. or less at normal pressure.
[0206] The water-soluble volatile organic solvent is preferably a solvent having a solubility of 5% by mass or more in water at 25°C, more preferably a solvent having a solubility of 30% by mass or more in water at 25°C, and further preferably a solvent that can be dissolved in water in any proportion.
[0207] Specific examples of the volatile organic solvent (E) include alcohol solvents such as ethanol, methanol, 1-propanol, and isopropyl alcohol; ketone solvents such as acetone and methyl ethyl ketone; and ether solvents such as 1,2-dimethoxyethane, 1,2-diethoxyethane, and tetrahydrofuran. Alcohol solvents are preferred from the viewpoints of excellent compatibility, prevention of phase separation of the components, and better storage stability.
[0208] When the content of the volatile organic solvent (E) is too much, the bonding strength may decrease. From the viewpoint of obtaining a desired viscosity as a dental adhesive composition, the content of the volatile organic solvent (E) is preferably 1 to 70% by mass, more preferably 5 to 50% by mass, and further preferably 10 to 30% by mass in the total mass of the dental adhesive composition.
[0209] <Filler (F)>
[0210] The dental adhesive composition contains a filler (F) in order to adjust the curability, the water absorption of the cured product, the mechanical strength and the handling property when the cured product is made into a film. Examples of the filler (F) include inorganic fillers, organic-inorganic composite fillers, and organic fillers.
[0211] The filler (F) may be used alone or in combination of two or more.
[0212] Examples of the inorganic filler include various glasses such as fused silica, quartz, soda-lime silicate glass, E glass, C glass, borosilicate glass (Pyrex (registered trademark) glass), strontium borosilicate glass, fluoroaluminosilicate glass, aluminosilicate glass, calcium fluoroaluminosilicate glass, strontium fluoroaluminosilicate glass, strontium calcium fluoroaluminosilicate glass, and barium glass (barium silicate glass, barium boroaluminosilicate glass, and barium fluoroaluminosilicate glass); lanthanum glass ceramics, various ceramics, aluminum oxide, and composite oxides (e.g., aluminum dioxide); Composite oxides containing silica, such as silicon-titania, silicon-titania-barium oxide, silicon-zirconia, silicon-alumina, and silicon-alumina-zirconia), ytterbium oxide, ytterbium fluoride coated with silicon dioxide, diatomaceous earth, kaolin, clay minerals (montmorillonite, etc.), activated clay, synthetic zeolite, mica, calcium fluoride, ytterbium fluoride, yttrium fluoride, calcium phosphate, barium sulfate, zirconium oxide, titanium oxide, hydroxyapatite, etc., each of which can be used alone or in combination of two or more.
[0213] Among the above, from the viewpoint of storage stability, fused silica and silica-zirconia are preferred, and fused silica is more preferred.
[0214] In one embodiment, the raw material of the inorganic filler preferably contains various glasses (containing silicon dioxide as the main component (containing 5% by mass or more, preferably 10% by mass or more of silicon dioxide), and containing oxides of heavy metals, boron, aluminum, etc. as needed).
[0215] From the viewpoint of operability and mechanical strength of the obtained dental adhesive composition, the average particle size of the inorganic filler is preferably 0.001 to 50 μm, more preferably 0.001 to 1 μm, further preferably 0.005 to 0.1 μm, and particularly preferably 0.005 to 0.05 μm. It should be noted that in the present invention, when the inorganic filler is surface treated as described later, the average particle size of the inorganic filler refers to the average particle size before the surface treatment. As a suitable embodiment, a dental adhesive composition in which the filler (F) is an inorganic filler can be listed.
[0216] Commercially available inorganic fillers may be used. Examples of commercially available inorganic fillers include silica such as AEROSIL (registered trademark) 90, AEROSIL (registered trademark) 130, AEROSIL (registered trademark) 150, AEROSIL (registered trademark) 200, AEROSIL (registered trademark) 255, AEROSIL (registered trademark) 300, AEROSIL (registered trademark) 380, AEROSIL (registered trademark) OX50, and AEROSIL (registered trademark) R972. Barium glass such as GM27884, 8235 (all made by Japan AEROSIL Co., Ltd.), GM27884, 8235 (all made by SCHOTT Co., Ltd.), and product code "E-3000" (made by ESTEC Co., Ltd.); strontium borosilicate glass (E-4000, made by ESSTECH Co., Ltd.), lanthanum glass ceramics (GM31684, made by SCHOTT Co., Ltd.), fluoroaluminosilicate glass (GM35429, G018-091, G018-117, made by SCHOTT Co., Ltd.), etc. As filler (F), from the viewpoint of adhesive strength, coating properties, etc., silica having a small primary particle size, such as AEROSIL (registered trademark) 90, AEROSIL (registered trademark) 130, AEROSIL (registered trademark) 150, AEROSIL (registered trademark) 200, AEROSIL (registered trademark) 255, AEROSIL (registered trademark) 300, AEROSIL (registered trademark) 380, AEROSIL (registered trademark) OX50, and AEROSIL (registered trademark) R972, is preferred.
[0217] The inorganic filler may be amorphous, crystalline, or a mixture of the two, but preferably contains at least an amorphous portion. The shape of the inorganic filler is not particularly limited, and can be appropriately selected and used.
[0218] In order to adjust the mechanical strength and fluidity of the dental adhesive composition and make the dental adhesive composition within the desired viscosity range, the inorganic filler is preferably surface-treated in advance using a known surface treatment agent such as a silane coupling agent. For example, by surface-treating the hydroxyl groups present on the surface of the inorganic filler using a surface treatment agent, an inorganic filler with the surface-treated hydroxyl groups can be obtained. The thickening effect caused by the compounding of the filler can be suppressed.
[0219] Examples of the surface treatment agent include vinyl trimethoxysilane, vinyl triethoxysilane, vinyl trichlorosilane, vinyl tri(β-methoxyethoxy)silane, 3-methacryloxypropyl trimethoxysilane, 8-methacryloxyoctyl trimethoxysilane, 11-methacryloxyundecyl trimethoxysilane, γ-glycidoxypropyl trimethoxysilane, γ-mercaptopropyl trimethoxysilane, and γ-aminopropyl triethoxysilane. Preferred are vinyl trimethoxysilane, 3-methacryloxypropyl trimethoxysilane, 8-methacryloxyoctyl trimethoxysilane, 11-methacryloxyundecyl trimethoxysilane, and γ-aminopropyl triethoxysilane.
[0220] As the surface treatment method, a known method can be used without particular limitation.
[0221] As a surface treatment method, there are, for example, the following methods: a method of spraying and adding the above-mentioned surface treatment agent while vigorously stirring the inorganic filler; a method of dispersing or dissolving the inorganic filler and the above-mentioned surface treatment agent in an appropriate solvent and then removing the solvent; or a method of hydrolyzing the alkoxy group of the above-mentioned surface treatment agent in an aqueous solution using an acid catalyst to convert it into a silanol group, attaching it to the surface of the inorganic filler in the aqueous solution, and then removing the water. In any method, the reaction between the surface of the inorganic filler and the above-mentioned surface treatment agent is usually terminated by heating in the range of 50 to 150° C., and the surface treatment is performed. It should be noted that the amount of surface treatment is not particularly limited. For example, 0.1 to 40 parts by mass of the surface treatment agent can be used relative to 100 parts by mass of the inorganic filler before treatment.
[0222] The organic-inorganic composite filler refers to a filler obtained by adding a monomer to the above-mentioned inorganic filler in advance, preparing the paste, polymerizing the paste, and then pulverizing the paste. The organic-inorganic composite filler refers to a filler containing an inorganic filler and a monomer polymer.
[0223] Examples of the monomer include a monomer (A) having an acidic group and a monomer (B) not having an acidic group, and a hydrophobic monomer (B-2) is preferred.
[0224] As the organic-inorganic composite filler, for example, Bis-GMA, 3G and a surface-treated silica filler are mixed, polymerized and then pulverized. The shape of the organic-inorganic composite filler is not particularly limited, and the particle size of the filler can be appropriately selected and used.
[0225] Furthermore, the organic-inorganic composite filler may be used alone or in combination of two or more.
[0226] From the viewpoint of mechanical strength, the organic-inorganic composite filler is also preferably surface-treated. Examples and preferred types of the surface treatment agent are the same as those for the inorganic filler.
[0227] The average particle size of the organic-inorganic composite filler is preferably 0.001 to 50 μm, more preferably 0.001 to 20 μm, and even more preferably 0.005 to 15 μm, from the viewpoint of the handleability and mechanical strength of the resulting dental adhesive composition.
[0228] Examples of the raw material of the organic filler include polymethyl methacrylate, polyethyl methacrylate, methyl methacrylate-ethyl methacrylate copolymer, cross-linked polymethyl methacrylate, cross-linked polyethyl methacrylate, polyamide, polyvinyl chloride, polystyrene, chloroprene rubber, nitrile rubber, ethylene-vinyl acetate copolymer, styrene-butadiene copolymer, acrylonitrile-styrene copolymer, acrylonitrile-styrene-butadiene copolymer, and the like. These may be used alone or as a mixture of two or more.
[0229] The shape of the organic filler is not particularly limited, and the particle size of the filler can be appropriately selected for use.
[0230] The average particle size of the organic filler is preferably 0.001 to 50 μm, more preferably 0.001 to 20 μm, and even more preferably 0.005 to 15 μm, from the viewpoint of the handleability and mechanical strength of the resulting dental adhesive composition.
[0231] It should be noted that, in this specification, the average particle size of the filler can be obtained by laser diffraction and scattering method, electron microscope observation of particles. Specifically, for the particle size measurement of 0.1 μm or more, the laser diffraction and scattering method is simple, and for the particle size measurement of ultrafine particles less than 0.1 μm, electron microscope observation is simple. 0.1 μm is a measured value based on the laser diffraction and scattering method. It should be noted that, in the case of particles formed by aggregation of primary particles, such as aggregated particles, there is an average particle size of primary particles and an average particle size of secondary particles, and the average particle size of the filler is set to the average particle size of the secondary particles whose particle size becomes larger.
[0232] Specifically, the laser diffraction scattering method can be measured on a volume basis using, for example, a laser diffraction particle size distribution measuring apparatus (SALD-2300: manufactured by Shimadzu Corporation) using a 0.2% sodium hexametaphosphate aqueous solution as a dispersion medium.
[0233] Specifically, regarding electron microscope observation, for example, an electron microscope (manufactured by Hitachi, Ltd., S-4000 type) photograph of particles can be taken, and the particle size of the particles (more than 200) observed in the unit field of view of the photograph is measured using image analysis type particle size distribution measurement software (Mac-View (manufactured by MOUNTECH)), thereby obtaining. At this time, the particle size is obtained in the form of the arithmetic mean of the maximum length and the minimum length of the particles, and the average particle size is calculated based on the number of particles and their particle size.
[0234] The refractive index of the filler (F) is not particularly limited, for example, it can be 1.35 or more and 2.00 or less. From the viewpoint of the transparency of the cured product, the refractive index of the filler (F) is preferably 1.40 or more and 1.70 or less. The refractive index of the filler (F) can be controlled by adjusting the type of the constituent of the filler (F) and / or the content ratio of the constituent. It should be noted that in this specification, the refractive index of the measurement object (filler (F), colorant, etc.) can be measured using an Abbe refractometer.
[0235] The content of the filler (F) is not particularly limited, but is preferably 0.1 to 30% by mass, more preferably 0.5 to 20% by mass, and even more preferably 1 to 10% by mass, based on the total mass of the dental adhesive composition, from the viewpoint of obtaining the desired viscosity of the dental adhesive composition, enabling the cured product to be made into a thin film, the water absorption of the cured product, the workability, and the mechanical strength of the cured product.
[0236] By combining the content of the filler (F) within the above range with other components, the dental adhesive composition can be within a desired viscosity range, and even if the adhesive layer as a cured product is very thin, a decrease in mechanical strength can be suppressed, and high mechanical strength that lasts for a long time can be easily obtained.
[0237] <Polymerization Accelerator (G)>
[0238] From the viewpoint of the mechanical strength of the cured product, the dental adhesive composition preferably contains a polymerization accelerator (G).
[0239] Examples of the polymerization accelerator (G) used in the present invention include amines, sulfinic acid and salts thereof, boric acid ester compounds, barbituric acid compounds, triazine compounds, copper compounds, tin compounds, vanadium compounds, halogen compounds, aldehydes, thiol compounds, sulfites, hydrogensulfites, and thiourea compounds.
[0240] The polymerization accelerator (G) may be contained alone or in combination of two or more.
[0241] Amines used as polymerization accelerators (G) are divided into aliphatic amines and aromatic amines. As aliphatic amines, for example, aliphatic primary amines such as n-butylamine, n-hexylamine, and n-octylamine; aliphatic secondary amines such as diisopropylamine, dibutylamine, and N-methylethanolamine; N-methyldiethanolamine, N-ethyldiethanolamine, N-n-butyldiethanolamine, N-lauryldiethanolamine, 2-(dimethylamino)ethyl methacrylate, N-methyldiethanolamine dimethacrylate, N-ethyldiethanolamine dimethacrylate, triethanolamine monomethacrylate, triethanolamine dimethacrylate, triethanolamine trimethacrylate, triethanolamine, trimethylamine, triethylamine, aliphatic tertiary amines such as tributylamine, etc. Among these, from the viewpoint of curability and storage stability of the dental adhesive composition, aliphatic tertiary amines are preferred, and N-methyldiethanolamine and triethanolamine are more preferably used.
[0242] Examples of the aromatic amines include N,N-bis(2-hydroxyethyl)-3,5-dimethylaniline, N,N-bis(2-hydroxyethyl)-p-toluidine, N,N-bis(2-hydroxyethyl)-3,4-dimethylaniline, N,N-bis(2-hydroxyethyl)-4-ethylaniline, N,N-bis(2-hydroxyethyl)-4-isopropylaniline, N,N-bis(2-hydroxyethyl)-4-tert-butylaniline, N,N-bis(2-hydroxyethyl)-3,5-diisopropylaniline, N,N-bis(2-hydroxyethyl)-3,5-di-tert-butylaniline, N,N-dimethylaniline, N,N-dimethyl-p-toluidine, N,N-dimethyl-m-toluidine, N,N-diethyl-p-toluidine, N,N- -Dimethyl-3,5-dimethylaniline, N,N-dimethyl-3,4-dimethylaniline, N,N-dimethyl-4-ethylaniline, N,N-dimethyl-4-isopropylaniline, N,N-dimethyl-4-tert-butylaniline, N,N-dimethyl-3,5-di-tert-butylaniline, ethyl 4-(N,N-dimethylamino)benzoate, methyl 4-(N,N-dimethylamino)benzoate, propyl 4-(N,N-dimethylamino)benzoate, n-butoxyethyl 4-(N,N-dimethylamino)benzoate, 2-(methacryloyloxy)ethyl 4-(N,N-dimethylamino)benzoate, 4-(N,N-dimethylamino)benzophenone, butyl 4-(N,N-dimethylamino)benzoate, etc. Among these, from the viewpoint of being able to impart excellent curability to the dental adhesive composition, it is preferred to use at least one selected from N,N-bis(2-hydroxyethyl)-p-toluidine, ethyl 4-(N,N-dimethylamino)benzoate, n-butoxyethyl 4-(N,N-dimethylamino)benzoate and 4-(N,N-dimethylamino)benzophenone.
[0243] Specific examples of sulfinic acid and salts thereof, boric acid ester compounds, barbituric acid compounds, triazine compounds, copper compounds, tin compounds, vanadium compounds, halogen compounds, aldehydes, thiol compounds, sulfites, hydrogensulfites, and thiourea compounds include those described in International Publication No. 2008 / 087977.
[0244] The content of the polymerization accelerator (G) used in the present invention is not particularly limited, but is preferably in the range of 0.01 to 10% by mass, more preferably in the range of 0.05 to 7% by mass, and even more preferably in the range of 0.1 to 5% by mass, based on the total mass of the dental adhesive composition, from the viewpoint of the curability and mechanical strength of the obtained dental adhesive composition.
[0245] The dental adhesive composition may further contain a fluoride ion releasing substance. By containing a fluoride ion releasing substance, a dental adhesive composition capable of imparting acid resistance to tooth substance can be obtained. Examples of the fluoride ion releasing substance include fluoride ion releasing polymers such as copolymers of methyl methacrylate and methacryloyl fluoride; metal fluorides such as sodium fluoride, potassium fluoride, sodium monofluorophosphate, lithium fluoride, and ytterbium fluoride; and the like. The above-mentioned fluoride ion releasing substances may contain one kind alone or two or more kinds in combination.
[0246] The content of the fluoride ion-releasing substance is preferably 0.0001 to 10% by mass, more preferably 0.005 to 5% by mass, and even more preferably 0.01% to 2% by mass, based on the total mass of the dental adhesive composition.
[0247] The dental adhesive composition may contain known additives within a range that does not reduce performance, such as polymerization inhibitors, antioxidants, colorants (pigments, dyes), ultraviolet absorbers, fluorescent agents, silane coupling agents, thickeners, and the like.
[0248] The additives may be used alone or in combination of two or more.
[0249] From the viewpoint of adjusting storage stability and curability, the dental adhesive composition of the present invention preferably includes a polymerization inhibitor. As the polymerization inhibitor, for example, hydroquinone, hydroquinone monomethyl ether, dibutylhydroquinone, dibutylhydroquinone monomethyl ether, tert-butylcatechol, 2-tert-butyl-4,6-dimethylphenol, 2,6-di-tert-butylphenol, 3,5-di-tert-butyl-4-hydroxytoluene, etc. can be listed. They can be used alone or in combination of two or more.
[0250] The content of the polymerization inhibitor is preferably 0.001 to 1.0% by mass in the total mass of the dental adhesive composition.
[0251] From the viewpoint of light stability for fluorescent lamps, LEDs, etc., which are called ambient light, and the viewpoint of inhibiting the discoloration of cured products, the dental adhesive composition of the present invention preferably includes an ultraviolet light absorber. As an ultraviolet light absorber, for example, 2-(2-hydroxyphenyl)benzotriazole, 2-(2-hydroxy-5-methylphenyl)benzotriazole, 2-(2-hydroxy-5-ethylphenyl)benzotriazole, 2-(2-hydroxy-5-propylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, 2-(3-tert-butyl-2-hydroxy-5-methylphenyl)-5-chloro-2H-benzotriazole (Tinuvin326) and other benzotriazole compounds and benzimidazole compounds can be listed, preferably Tinuvin326. They can be used alone or in combination of two or more.
[0252] In the dental adhesive composition of the present invention, from the viewpoint of adhesion to tooth substance and long-term mechanical strength, in addition to the surface treatment agent for the filler, a silane coupling agent is preferably included. Examples of the silane coupling agent include vinyl trimethoxysilane, vinyl triethoxysilane, vinyl trichlorosilane, vinyl tri(β-methoxyethoxy)silane, 3-methacryloxypropyl trimethoxysilane, 8-methacryloxyoctyl trimethoxysilane, 11-methacryloxy undecyl trimethoxysilane, γ-glycidoxypropyl trimethoxysilane, γ-mercaptopropyl trimethoxysilane, γ-aminopropyl triethoxysilane, 3-(meth)acryloxypropyl methyl dimethoxysilane, 3-(meth)acryloxypropyl methyl diethyl Oxysilane, 3-(meth)acryloxypropyldimethylmonomethoxysilane, from the viewpoint of adhesion, preferably vinyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 8-methacryloxyoctyltrimethoxysilane, 11-methacryloxyundecyltrimethoxysilane, γ-aminopropyltriethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropylmethyldiethoxysilane, 3-(meth)acryloxypropyldimethylmonomethoxysilane, and hydrolyzates thereof.
[0253] The above-mentioned silane coupling agents may be used alone or in combination of two or more.
[0254] The content of the silane coupling agent is preferably 0.001 to 30% by mass, more preferably 0.05 to 20% by mass, and even more preferably 0.1% to 10% by mass, based on the total mass of the dental adhesive composition.
[0255] As the dental adhesive composition, an example of a suitable composition ratio is shown.
[0256] The dental adhesive composition preferably contains, in the total mass of the composition, 1 to 50 mass % of a monomer (A) having an acidic group, 0.1 to 20 mass % of a monomer (B-1) having three or more polymerizable groups in one molecule, 5 to 60 mass % of a hydrophobic monomer (B-2), 5 to 60 mass % of a hydrophilic monomer (B-3), 0.01 to 10 mass % of a photopolymerization initiator (C-1), 1 to 50 mass % of water (D), 1 to 70 mass % of a volatile organic solvent (E), 0.1 to 30 mass % of a filler (F), and 0.0 1 to 10% by mass, more preferably 1 to 30% by mass of a monomer (A) having an acidic group, 0.5 to 15% by mass of a monomer (B-1) having three or more polymerizable groups in one molecule, 10 to 50% by mass of a hydrophobic monomer (B-2), 7 to 50% by mass of a hydrophilic monomer (B-3), 0.05 to 7% by mass of a photopolymerization initiator (C-1), 5 to 30% by mass of water (D), 5 to 50% by mass of a volatile organic solvent (E), 0.5 to 20% by mass of a filler (F), and 0.05 to 7% by mass of a polymerization accelerator (G).
[0257] Regarding the method for producing a dental adhesive composition, the composition comprises a monomer having an acidic group (A), a monomer not having an acidic group (B), a polymerization initiator (C), water (D), a volatile organic solvent (E) and a filler (F), and further comprises other components as required, and can be easily produced by a method known to those skilled in the art.
[0258] The dental adhesive composition of the present invention can be suitably used as a dental adhesive material or a dental coating material, and can be particularly suitably used as a dental adhesive material or a dental coating material used for resin coating applications.
[0259] The dental adhesive composition of the present invention has a viscosity of less than 40 cps at 30°C using a B-type viscometer, and can achieve a thin coating layer within a temperature range (eg, 35°C or less) assumed for use at room temperature in dental clinics.
[0260] The dental adhesive composition of the present invention may be combined with a dental etching material, a dental pretreatment agent, etc. The dental etching material and the dental pretreatment agent may be used alone or in combination.
[0261] The dental etching material, the dental pretreatment agent, and the like are not particularly limited, and commercially available products may be used.
[0262] <Specific application methods and steps>
[0263] The dental adhesive composition is applied to the tooth surface to be applied. After the dental adhesive composition is applied, water (D) and volatile organic solvent (E) in the dental adhesive composition are removed by blowing air at a pressure appropriately adjusted so that the dental adhesive composition does not move from the applied part.
[0264] Thereafter, in the case of the dental adhesive composition blended with the photopolymerization initiator (C-1), light is irradiated using a dental light irradiator to cure the composition.
[0265] In the case of a dental adhesive composition containing a chemical polymerization initiator (C-2), the composition may be left to stand until curing is complete, and then filled with a separately prepared dental composite resin as needed.
[0266] The dental composite resin is not particularly limited, and a commercially available product can be used.
[0267] When a dental etching material, a dental pretreatment agent, etc. are combined with the dental adhesive composition, the dental etching material, the dental pretreatment agent, etc. are used before applying the dental adhesive composition.
[0268] Example
[0269] Hereinafter, the present invention will be described in detail with reference to Examples and Comparative Examples, but the present invention is not limited to the Examples. It should be noted that parts in the examples are parts by mass unless otherwise specified.
[0270] Next, the components of the dental adhesive compositions of Examples and Comparative Examples are described below together with abbreviations.
[0271] [Monomer having an acidic group (A)]
[0272] MDP: 10-methacryloyloxydecyl dihydrogen phosphate
[0273] GDMP: 1,3-glyceryl dimethacrylate phosphate
[0274] 4-META: 4-Methacryloyloxyethyl trimellitic anhydride
[0275] [Monomer not having an acidic group (B)]
[0276] Monomer having three or more polymerizable groups in one molecule (B-1)
[0277] TMPMA: trimethylolpropane tri(meth)acrylate (solubility in water at 25°C: less than 10% by mass)
[0278] U4TH: N,N-(2,2,4-trimethylhexamethylene)bis[2-(aminocarboxy)propane-1,3-diol]tetramethacrylate (solubility in water at 25°C: less than 10% by mass)
[0279] TAC4: N,N',N",N''-tetraacryloyltriethylenetetramine (solubility in water at 25°C: 10% by mass or more)
[0280] DTMP: di(trimethylolpropane)tetramethacrylate (solubility in water at 25°C: less than 10% by mass)
[0281] Bis-4: Compound of formula (3) (solubility in water at 25°C: less than 10% by mass)
[0282]
[0283] ·Hydrophobic monomer (B-2)
[0284] Bis-GMA: 2,2-bis[4-(2-hydroxy-3-methacryloyloxypropoxy)phenyl]propane
[0285] 3G: Triethylene glycol dimethacrylate
[0286] MAEA: N-methacryloyloxyethylacrylamide
[0287] UDMA: [2,2,4-trimethylhexamethylenebis(2-carbamoyloxyethyl)] dimethacrylate
[0288] NPG: Neopentyl glycol dimethacrylate
[0289] ·Hydrophilic monomer (B-3)
[0290] DEAA: N,N-diethylacrylamide
[0291] HEMA: 2-Hydroxyethyl Methacrylate
[0292] #801: 1,2-Bis(3-methacryloyloxy-2-hydroxypropoxy)ethane
[0293] [Photopolymerization initiator (C-1)]
[0294] CQ: dl-Camphorquinone
[0295] BAPO: Bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide
[0296] TMDPO: 2,4,6-trimethylbenzoyldiphenylphosphine oxide
[0297] [Water (D)]
[0298] Purified water
[0299] [Volatile organic solvents (E)]
[0300] Ethanol
[0301] acetone
[0302] [Filler (F)]
[0303] R972: AEROSIL Corporation, Japan, hydrophobic fumed silica, ultrafine silica "AEROSIL (registered trademark) R972", average particle size: 16 nm (silicon dioxide), refractive index: 1.46
[0304] [Polymerization accelerator (G)]
[0305] DABE: 4-(N,N-dimethylamino)benzoic acid ethyl ester
[0306] DEPT: N,N-bis(2-hydroxyethyl)-p-toluidine
[0307] [other]
[0308] BHT: 3,5-di-tert-butyl-4-hydroxytoluene (polymerization inhibitor)
[0309] KBM-503: 3-methacryloxypropyltrimethoxysilane (silane coupling agent)
[0310] Sodium fluoride
[0311] <Examples 1 to 21 and Comparative Examples 1 to 7>
[0312] [Preparation of dental adhesive composition]
[0313] Among the raw materials shown in Tables 1 to 3, the components other than filler, water, and volatile organic solvent were first mixed, and then the filler was added and mixed, and then water and volatile organic solvent were added to obtain a mixture. The mixture was stirred at room temperature (23° C.) in a dark place to make it uniform, and then ultrasonic degassing was performed to prepare a liquid dental adhesive composition.
[0314] Test Example 1 Water Absorption
[0315] The liquid dental adhesive composition made is put into a screw bottle, and air is continuously blown, so that the water and volatile organic solvent in the dental adhesive composition are volatilized. Then, the composition is filled into a mold (diameter 15mm, thickness 1.0mm) made of SUS, and after the upper and lower (faces of diameter 15mm) are clamped with polyester film, a slide is used for crimping. Then, a dental visible light irradiator (PENCURE 2000, MORITA company system) is used across a slide in a crimped state, and light irradiation (light irradiation for 50 seconds for a single side totaling) is performed from the upper and lower parts of the aforementioned composition according to the standard mode every 10 seconds for a single side, so that the composition is cured to obtain a cured product. About the sample of the cured product, 10 pieces are respectively made in the embodiment and the comparative example, and the cured product is taken out from the mold, and after removing the burrs, the mass weighed as the sample is set to m1.
[0316] Thereafter, while immersed in distilled water (30 mL) in the container, 5 sheets were placed in a thermostat set at 37° C. for 24 hours, and the remaining 5 sheets were placed in a thermostat set at 37° C. for 7 days. Next, the sheets were taken out from the distilled water, and the attached water was removed, and the mass obtained by weighing was set to m2.
[0317] The water absorption rate was calculated according to the following formula: The water absorption rate was measured for each sample of the cured product, and the average value was calculated (n=5).
[0318] W sp (%) = (m2-m1) / m1(g / g)×100
[0319] m1: Sample mass after immersion in water for 24 hours (μg)
[0320] m2: Mass of sample before immersion in water (μg)
[0321] From the viewpoint of mechanical strength of the cured product, adhesion to tooth structure, and durability, the water absorption rate (hereinafter also referred to as "initial water absorption rate") of the cured product of the dental adhesive composition of the present invention when immersed at 37°C for 24 hours is 4.0% or less, preferably 3.5% or less, more preferably 3.0% or less, further preferably 2.5% or less, and particularly preferably less than 2.3%. If the water absorption rate exceeds 4.0%, the mechanical strength of the cured product and the adhesion to tooth structure may be insufficient.
[0322] From the viewpoint of the mechanical strength of the cured product that lasts for a long time, and the adhesion and durability to tooth texture, the water absorption rate of the cured product of the dental adhesive composition of the present invention when immersed at 37°C for 7 days (hereinafter also referred to as "durable water absorption rate") is preferably 7.5% or less, more preferably 7.0% or less, further preferably 6.5% or less, and particularly preferably less than 6.0%.
[0323] Test Example 2 Shear Bond Strength (Enamel, Dentin)
[0324] The dental adhesive composition of the present invention also has excellent bonding strength to tooth structure for a long time, can protect exposed tooth structure for a long time in resin coating applications, and can be suitably used in indirect restoration methods. Furthermore, the dental adhesive composition of the present invention also has excellent bonding strength to tooth structure and exhibits good caries sealing properties, and therefore can also be suitably used as a dental adhesive composition for general direct restoration methods.
[0325] This test example is a test system intended for direct restoration. When used for resin coating, there is essentially no difference from the viewpoint of adhesion to tooth structure. In this test example, the bonding strength to tooth structure for resin coating can also be evaluated.
[0326] The test was carried out in accordance with ISO29022:2013. The details are as follows.
[0327] The labial surface of the bovine tooth was polished with #80 silicon carbide paper (manufactured by Nippon Kenshi Co., Ltd.) under running water to obtain a sample in which the flat surface of the enamel was exposed and a sample in which the flat surface of the dentine was exposed.
[0328] First, using a sample in which the flat surface of the enamel was exposed, the shear adhesive strength to the enamel was measured by the following method.
[0329] In a separately prepared mold having 15 holes (15-hole mold, manufactured by Ultradent, The bottom surface of the 25 mm × 25 mm high surface was affixed with adhesive tape, and the bovine teeth of the aforementioned sample were fixed thereon.
[0330] Next, a dental impression tray resin (trade name "tray resin II", manufactured by Matsukaze Co., Ltd.) was filled into the mold and allowed to stand for about 30 minutes to cure the dental impression tray resin to obtain a composite of bovine tooth and the resin cured product. The composite was taken out from the mold as a sample.
[0331] The composite was made in a state where the bovine teeth were exposed on the upper surface of the resin cured product. The upper surface of the sample was ground under running water using #600 silicon carbide paper (manufactured by Nippon Kenji Co., Ltd.) to a size that could ensure the bonding surface ( The bonding surface was washed with water using ultrasonic waves for 5 minutes.
[0332] Next, the dental adhesive composition (adhesive) prepared in each example and comparative example was applied to the surface of the bovine tooth and allowed to stand for 3 seconds, and then water and volatile organic solvents were volatilized by gentle air blowing. Next, a dental visible light irradiator (PENCURE 2000, manufactured by MORITA) was used to irradiate light for 10 seconds in a standard mode to photocure the adhesive.
[0333] Will be prepared separately The CR filling mold (Bonding Mold Insert, manufactured by Ultradent) was mounted on a dedicated tool (Bonding Clamp, manufactured by Ultradent). Next, the CR filling mold mounted on the dedicated tool was lowered to allow the CR filling mold to adhere closely to the bonding surface of the sample, thereby fixing the sample.
[0334] Next, CLEARFIL (registered trademark) AP-X (manufactured by Kuraray Noritake Dental Co., Ltd.) is thinly filled into the hole of the aforementioned CR filling mold in a manner that the thickness is within 1 mm. Thereafter, CLEARFIL (registered trademark) AP-X is again filled into the aforementioned CR filling mold (to about 2 / 3 of the mold, with a thickness of about 2 mm), and light irradiation is performed for 20 seconds in a standard mode using a dental visible light irradiator (PENCURE 2000, manufactured by MORITA), thereby curing CLEARFIL (registered trademark) AP-X. A sample is taken out from the aforementioned CR filling mold and used as a test sample for the bonding test. 20 test samples of each bonding test are prepared.
[0335] Next, the bonding test samples were immersed in distilled water in a container and placed in a thermostat set to 37°C for 24 hours. For 10 samples, the shear bonding strength (hereinafter also referred to as "initial shear bonding strength") was measured immediately after they were taken out of the distilled water. In each table, the average value of the measurement results is shown as "initial". For the remaining 10 samples, in order to evaluate the bonding durability, a thermal cycle of further alternating immersion in cold water at 4°C and warm water at 60°C for 1 minute was performed for 4000 cycles as one cycle, and the shear bonding strength (hereinafter also referred to as "durable shear bonding strength") was measured. In each table, the average value of the measurement results is shown as "durable".
[0336] Regarding the measurement of bonding strength (shear bonding strength), the bonding test sample was mounted on a dedicated bracket (Test Base Clamp, manufactured by Ultradent), and a dedicated clamp (Crosshead Assembly, manufactured by Ultradent) and a universal testing machine (manufactured by Shimadzu Corporation) were used. The slider speed was set to 1 mm / min for measurement, and the average value is shown in the table (n=10).
[0337] The shear bond strength for dentin was measured in the same manner as the shear bond strength for enamel, and the average values are shown in the respective tables (n=10).
[0338] The initial shear bond strength of the dental adhesive composition of the present invention to enamel is preferably 15 MPa or more, more preferably 20 MPa or more, and even more preferably 25 MPa or more.
[0339] The durable shear adhesive strength to enamel is preferably 10 MPa or more, more preferably 15 MPa or more, and even more preferably 20 MPa or more.
[0340] The initial shear bond strength of the dental adhesive composition of the present invention to dentin is preferably 15 MPa or more, more preferably 20 MPa or more, and even more preferably 25 MPa or more.
[0341] The durable shear bond strength to dentin is preferably 10 MPa or more, more preferably 15 MPa or more, and even more preferably 20 MPa or more.
[0342] Test Example 3 Tensile Strength Test
[0343] The prepared dental adhesive compositions were added in appropriate amounts to a glass beaker and continuously blown with stirring to volatilize water and volatile organic solvents contained in the dental adhesive compositions. A polyester film was placed on a glass slide, and a 1 mm×1 mm×10 mm Teflon (registered trademark) mold was set thereon.
[0344] Next, the dental adhesive composition after evaporation of water and volatile organic solvent was poured into a Teflon (registered trademark) mold, sandwiched between polyester and a slide glass, and then irradiated with light in the normal mode of a dental visible light irradiator (PENCURE 2000, manufactured by MORITA) for 10 seconds on both the front and back sides to be photocured.
[0345] After the obtained cured product was taken out from the Teflon (registered trademark) mold, the excess burrs were removed. Ten samples were prepared for each test. The prepared samples were placed in a thermostat set to 37°C in a state of being immersed in distilled water in a container for 24 hours. The tensile strength (n=5) was measured using a universal testing machine (Autograph AG-I 100kN, manufactured by Shimadzu Corporation) at a slider speed of 1.0mm / min, and the average value was calculated. In each table, the average value of the measurement results is shown as "initial".
[0346] The remaining 5 were immersed in distilled water in a container and placed in a thermostat set at 37°C for 7 days, and then the tensile strength was measured (n=5) using a universal testing machine (Autograph AG-I 100 kN, manufactured by Shimadzu Corporation) at a slide speed of 1.0 mm / min, and the average value was calculated. In each table, the average value of the measurement results is shown as "Durability".
[0347] From the viewpoint of the mechanical strength of the cured product and the adhesion and durability to tooth texture, the tensile strength of the dental adhesive composition of the present invention when immersed at 37°C for one day (hereinafter also referred to as "initial tensile strength") is preferably 40 MPa or more, more preferably 45 MPa or more, and even more preferably 50 MPa or more.
[0348] From the viewpoint of the mechanical strength of the cured product that lasts for a long time, as well as the adhesion and durability to tooth texture, the tensile strength of the dental adhesive composition of the present invention when immersed at 37°C for 7 days (hereinafter also referred to as "durable tensile strength") is preferably 25 MPa or more, more preferably 35 MPa or more, and even more preferably 45 MPa or more.
[0349] Test Example 4: Determination of coating thickness
[0350] The labial surface of the front teeth of the mandibular teeth of cattle was ground with #80 silicon carbide paper (manufactured by Nippon Kenshi Co., Ltd.) under running water to obtain a sample in which the flat surface of the dentine was exposed. The obtained sample was further ground with #1000 silicon carbide paper (manufactured by Nippon Kenshi Co., Ltd.) under running water. After the grinding was completed, the water on the surface was blown to dry it. An adhesive tape with a circular hole of 3 mm in diameter and a thickness of about 150 μm was pasted on the smooth surface after drying to define the bonding area.
[0351] Use the FINE <silver>(Kuraray Noritake Dental Co., Ltd.) The dental adhesive composition prepared in each embodiment and comparative example was applied to the circular hole, and after being left for 10 seconds, the dental adhesive composition in the circular hole was dried as a whole by gentle blowing at weak to medium pressure until the liquid surface no longer moved. In order to dry it reliably, it was dried by blowing for more than 5 seconds. Then, light was irradiated for 10 seconds using a dental visible light irradiator (PENCURE 2000, made by MORITA), thereby curing the applied dental adhesive composition to form an adhesive layer.
[0352] The surface of the cured product of the obtained dental adhesive composition was filled with a dental filling composite resin (manufactured by Kuraray Noritake Dental Co., Ltd., trade name "CLEARFIL (registered trademark) MAJESTY (registered trademark) ES FLOW") and covered with a release film (polyester). Next, a slide glass was placed on the release film and pressed to smooth the coated surface of the composite resin. Next, the composite resin was irradiated with light for 10 seconds using the irradiator "PENCURE 2000" through the release film to cure the composite resin. Next, the sample was placed in a thermostat set to 37° C. for 24 hours in a state where it was immersed in distilled water in a container.
[0353] After being placed for 24 hours, the sample was cut in half with the bonding surface exposed by a diamond cutter (Buchler, ISOMET1000, using a diamond cutting grindstone), and the sample was corrected in a manner that the observation surface can be set in parallel by using #80 silicon carbide paper (Japan Ken Paper Co., Ltd.), and then, the observation surface was precisely ground in the order of #1200, #3000, and #8000 by using a polishing film (Sumitomo 3M Co., Ltd.). The obtained ground sample was fixed to a sample stage by using a carbon double-sided tape (HIS2166, Hitachi High-Tech Fielding Co., Ltd.), and the film thickness was measured at 3000 times in the low vacuum mode of a scanning electron microscope (Hitachi High-Technologies Co., Ltd., SU3500).
[0354] Specifically, as described above, in the cross section of the sample that includes a circular hole and is cut in half in a manner that the adhesive surface is exposed, in order to suppress the thickness deviation of the adhesive layer measured, 1 mm at each end is removed, and the average value of the thickness of the adhesive layer at three points randomly selected within the range of 1 mm in the center is measured on the software as the coating thickness. Three samples are prepared for each, and the average value is set as the coating thickness (n=3).
[0355] From the viewpoint of the form of the abutment tooth, the coating thickness is preferably 12 μm or less, more preferably 11 μm or less, and even more preferably 10 μm or less.
[0356] Test Example 5 Measurement of Viscosity at 30°C Using a B-Type Viscometer
[0357] 0.7 mL of the dental adhesive composition prepared in each of the above examples or comparative examples was added dropwise to a rotational viscometer (manufactured by Toki Sangyo Co., Ltd., "VISCOMETER TV-100"), and stirring was started under the conditions of a measurement temperature of 30°C and a rotation speed of 10 rpm. Three minutes after the start of stirring, the viscosity at 30°C was measured. Three samples were prepared for each dental adhesive composition, and the average value of these measured values was defined as the viscosity of the dental adhesive composition at 30°C based on a B-type viscometer.
[0358]
[0359] [Table 2]
[0360]
[0361] In the table, the monomer (B-1) having three or more polymerizable groups in one molecule, the hydrophobic monomer (B-2), and the hydrophilic monomer (B-3) all refer to monomers having no acidic group.
[0362] [Table 3]
[0363]
[0364] In the table, the monomer (B-1) having three or more polymerizable groups in one molecule, the hydrophobic monomer (B-2), and the hydrophilic monomer (B-3) all refer to monomers having no acidic group.
[0365] As shown in Tables 1 and 2, the results of the dental adhesive compositions of Examples are as follows.
[0366] The initial water absorption is below 3.8%, and the durable water absorption is below 7.9%.
[0367] For enamel, the initial shear bond strength is 16 MPa or more, and the durable shear bond strength is 10 MPa or more.
[0368] For dentin, the initial shear bond strength is 20 MPa or more, and the durable shear bond strength is 14 MPa or more.
[0369] Regarding mechanical strength, the initial tensile strength was 42 MPa or more, and the endurance tensile strength was 28 MPa.
[0370] The film thickness is 12 μm or less and the viscosity is 38 cps or less.
[0371] On the other hand, as shown in Table 3, among the comparative examples, Comparative Example 1 which does not contain the monomer (B-1) having three or more polymerizable groups in one molecule and Comparative Example 2 which does not contain the filler (F) have an initial tensile strength of less than 34 MPa and a durable tensile strength of less than 17 MPa.
[0372] The viscosity of Comparative Example 3 containing no volatile organic solvent (E) was 820 cps, and the film thickness was 40 μm.
[0373] The initial water absorption of Comparative Examples 4 and 5 not containing the hydrophobic monomer (B-2) was 6.5% or more, and the initial tensile strength was 30 MPa or less.
[0374] The viscosity of Comparative Example 6 was as high as 45 cps, and the coating thickness was as large as 14 μm, and a thin film adhesive layer could not be obtained.
[0375] In Comparative Example 7 which did not contain the hydrophilic monomer (B-3), the initial bonding strength to the enamel was 13 MPa, the durable bonding strength was 9 MPa, the coating thickness was 18 μm, and the viscosity was as high as 70 cps.
[0376] Industrial Applicability
[0377] The dental adhesive composition of the present invention can be suitably used for filling purposes in dental treatment, and coating purposes for caries and bridge abutments. In the resin coating application requiring thin filming, even if the thickness of the coating is 12 μm or less (preferably less than 10 μm), the cured product has high mechanical strength for a long time. Therefore, even if the layer of the cured product formed after the operation of volatilizing the solvent component (blowing, etc.) is thinner than expected due to the change in layer thickness due to the degree of blowing, the mechanical strength of the cured product will not continue to decrease for a long time. Therefore, from the viewpoint that strict operation is not required during use, it is particularly advantageous in the resin coating application.< / silver>
Claims
1. A dental adhesive composition comprising: a monomer having an acidic group (A), a monomer not having an acidic group (B), a polymerization initiator (C), water (D), a volatile organic solvent (E) and a filler (F), The monomer (B) having no acidic group includes: a monomer (B-1) having three or more polymerizable groups in one molecule, a hydrophobic monomer (B-2) having one or two polymerizable groups in one molecule, and a hydrophilic monomer (B-3) having one or two polymerizable groups in one molecule. The viscosity based on B-type viscometer at 30°C is less than 40cps, The water absorption of the cured product is 4.0% or less.
2. The dental adhesive composition according to claim 1, wherein The monomer (B-1) having three or more polymerizable groups in one molecule includes a hydrophobic compound.
3. The dental adhesive composition according to claim 1 or 2, wherein The monomer (B-1) having three or more polymerizable groups in one molecule includes a compound having a urethane bond.
4. The dental adhesive composition according to any one of claims 1 to 3, wherein The monomer (B-1) having three or more polymerizable groups in one molecule includes an aliphatic compound.
5. The dental adhesive composition according to any one of claims 1 to 4, wherein The content of the monomer (B-1) having three or more polymerizable groups in one molecule is 0.1 to 20 parts by mass in 100 parts by mass of all monomer components.
6. The dental adhesive composition according to any one of claims 1 to 5, wherein The polymerizable group possessed by the monomer (B-1) having three or more polymerizable groups in one molecule is a (meth)acryloyloxy group.
7. The dental adhesive composition according to any one of claims 1 to 6, wherein The polymerization initiator (C) contains at least one selected from the group consisting of (bis)acylphosphine oxides, α-diketones and coumarins.
8. The dental adhesive composition according to any one of claims 1 to 7, wherein The volatile organic solvent (E) includes an alcohol solvent.
9. The dental adhesive composition according to any one of claims 1 to 8, wherein At least one of the monomer (B-1) having three or more polymerizable groups in one molecule, the hydrophobic monomer (B-2) having one or two polymerizable groups in one molecule, and the hydrophilic monomer (B-3) having one or two polymerizable groups in one molecule contains a monomer having a (meth)acrylamide group.
10. The dental adhesive composition according to claim 9, wherein The hydrophobic monomer (B-2) having one or two polymerizable groups in one molecule includes a monomer having a (meth)acrylamide group.
11. The dental adhesive composition according to any one of claims 1 to 10, wherein The monomer (A) having an acidic group includes a monomer having a phosphoric acid group and having one polymerizable group in one molecule.
12. The dental adhesive composition according to claim 11, wherein The content of the monomer having a phosphoric acid group and having one polymerizable group in one molecule is 90 parts by mass or more in 100 parts by mass of the total monomer (A) having an acidic group contained in the dental adhesive composition.
13. The dental adhesive composition according to any one of claims 1 to 12, wherein The monomer (B-1) having three or more polymerizable groups in one molecule includes a hydrophobic compound, and all polymerizable groups of the hydrophobic compound are (meth)acryloyloxy groups.
14. The dental adhesive material according to any one of claims 1 to 13.
15. The dental coating material according to any one of claims 1 to 13.
Citation Information
Patent Citations
Visible-rays-induced polymerization initiator and visible-rays-polymerizable composition
JP1997003109A
Adhesive composition
JP1998245525A
Dental adhesive composition
JP2005179282A
Adhesive for dental use
JP2007223955A
Dental bonding material and composite resin, and composition suitable therefor
JP2008260751A